Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2022)
A dataset containing 14129650 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is one of (Ornithorhynchus anatinus (Shaw, 1799), Tachyglossus aculeatus (Shaw, 1792), Zaglossus bruijni (Peters & Doria, 1876), Cyclopes didactylus (Linnaeus, 1758), Myrmecophaga tridactyla Linnaeus, 1758, Tamandua mexicana (Saussure, 1860), Tamandua tetradactyla (Linnaeus, 1758), Choloepus hoffmanni Peters, 1858, Choloepus didactylus (Linnaeus, 1758), Bradypus variegatus Schinz, 1825, Bradypus tridactylus Linnaeus, 1758, Priodontes maximus (Kerr, 1792), Tolypeutes matacus (Desmarest, 1804), Cabassous centralis (Miller, 1899), Euphractus sexcinctus (Linnaeus, 1758), Zaedyus pichiy (Desmarest, 1804), Chaetophractus nationi (Thomas, 1894), Chaetophractus villosus (Desmarest, 1804), Chaetophractus vellerosus (Gray, 1865), Dasypus novemcinctus Linnaeus, 1758, Procavia capensis (Pallas, 1766), Heterohyrax brucei (Gray, 1868), Elephas maximus Linnaeus, 1758, Loxodonta africana (Blumenbach, 1797), Orycteropus afer (Pallas, 1766), Geogale aurita Milne-Edwards & A.Grandidier, 1872, Microgale talazaci Major, 1896, Microgale dobsoni Thomas, 1884, Microgale cowani Thomas, 1882, Limnogale mergulus Major, 1896, Tenrec ecaudatus (Schreber, 1778), Setifer setosus (Schreber, 1778), Amblysomus hottentotus (A.Smith, 1829), Chrysochloris asiatica (Linnaeus, 1758), Macroscelides proboscideus (Shaw, 1800), Petrodromus tetradactylus Peters, 1846, Elephantulus edwardii (A.Smith, 1839), Elephantulus rozeti (Duvernoy, 1833), Elephantulus myurus Thomas & Schwann, 1906, Elephantulus brachyrhynchus (A.Smith, 1836), Elephantulus rufescens (Peters, 1878), Elephantulus intufi (A.Smith, 1836), Rhynchocyon petersi Bocage, 1880, Catagonus wagneri (Rusconi, 1930), Pecari tajacu (Linnaeus, 1758), Babyrousa babyrussa (Linnaeus, 1758), Potamochoerus porcus (Linnaeus, 1758), Sus cebifrons Heude, 1888, Sus scrofa Linnaeus, 1758, Phacochoerus aethiopicus (Pallas, 1766), Phacochoerus africanus (Gmelin, 1788), Eschrichtius robustus (Lilljeborg, 1861), Balaenoptera musculus (Linnaeus, 1758), Balaenoptera acutorostrata Lacépède, 1804, Balaenoptera physalus (Linnaeus, 1758), Megaptera novaeangliae (Borowski, 1781), Balaena mysticetus Linnaeus, 1758, Phocoena phocoena (Linnaeus, 1758), Monodon monoceros Linnaeus, 1758, Orcinus orca (Linnaeus, 1758), Stenella longirostris (Gray, 1828), Tursiops truncatus (Montagu, 1821), Globicephala macrorhynchus Gray, 1846, Hippopotamus amphibius Linnaeus, 1758, Tragulus javanicus (Osbeck, 1765), Tragulus napu (F.Cuvier, 1822), Aepyceros melampus (Lichtenstein, 1812), Oreotragus oreotragus (Zimmermann, 1783), Neotragus moschatus (Von Dueben, 1846), Antilope cervicapra (Linnaeus, 1758), Gazella dorcas (Linnaeus, 1758), Gazella spekei Blyth, 1863, Gazella subgutturosa (Güldenstaedt, 1780), Gazella leptoceros (F.Cuvier, 1842), Gazella cuvieri (Ogilby, 1841), Eudorcas thomsonii (Günther, 1884), Nanger dama (Pallas, 1766), Nanger granti (Brooke, 1872), Nanger soemmerringii (Cretzschmar, 1828), Antidorcas marsupialis (Zimmermann, 1780), Litocranius walleri (Brooke, 1879), Madoqua kirkii (Günther, 1880), Madoqua guentheri Thomas, 1894, Raphicerus campestris (Thunberg, 1811), Philantomba monticola (Thunberg, 1789), Cephalophus dorsalis Gray, 1846, Cephalophus jentinki Thomas, 1892, Cephalophus rufilatus Gray, 1846, Cephalophus silvicultor (Afzelius, 1815), Cephalophus niger Gray, 1846, Oreamnos americanus (Blainville, 1816), Budorcas taxicolor Hodgson, 1850, Ammotragus lervia (Pallas, 1777), Ovibos moschatus (Zimmermann, 1780), Naemorhedus caudatus (Milne-Edwards, 1867), Hemitragus jemlahicus (C.H.Smith, 1826), Hemitragus hylocrius (Ogilby, 1838), Rupicapra rupicapra (Linnaeus, 1758), Ovis dalli Nelson, 1884, Ovis canadensis Shaw, 1804, Ovis aries Linnaeus, 1758, Capra falconeri (Wagner, 1839), Capra caucasica Güldenstaedt & Pallas, 1783, Capra hircus Linnaeus, 1758, Capra nubiana F.Cuvier, 1825, Capra ibex Linnaeus, 1758, Capra sibirica (Pallas, 1776), Taurotragus derbianus (Gray, 1847), Boselaphus tragocamelus (Pallas, 1766), Syncerus caffer (Sparrman, 1779), Bubalus bubalis (Linnaeus, 1758), Bubalus depressicornis (C.H.Smith, 1827), Tragelaphus eurycerus (Ogilby, 1837), Tragelaphus spekii Speke, 1863, Tragelaphus angasii Angas, 1849, Tragelaphus imberbis (Blyth, 1869), Tragelaphus strepsiceros (Pallas, 1766), Bos javanicus d'Alton, 1823, Bos taurus Linnaeus, 1758, Bos grunniens Linnaeus, 1766, Bos frontalis Lambert, 1804, Bison bison (Linnaeus, 1758), Kobus leche Gray, 1850, Kobus ellipsiprymnus (Ogilby, 1833), Kobus megaceros (Fitzinger, 1855), Kobus kob (Erxleben, 1777), Addax nasomaculatus (Blainville, 1816), Oryx leucoryx (Pallas, 1777), Oryx gazella (Linnaeus, 1758), Oryx dammah (Cretzschmar, 1827), Hippotragus equinus (É.Geoffroy Saint-Hilaire, 1803), Hippotragus niger (Harris, 1838), Damaliscus lunatus (Burchell, 1823), Damaliscus pygargus (Pallas, 1767), Connochaetes taurinus (Burchell, 1823), Alcelaphus buselaphus (Pallas, 1766), Elaphodus cephalophus Milne-Edwards, 1872, Muntiacus muntjak (Zimmermann, 1780), Muntiacus reevesi (Ogilby, 1839), Elaphurus davidianus Milne-Edwards, 1866, Dama dama (Linnaeus, 1758), Cervus elaphus Linnaeus, 1758, Cervus nippon Temminck, 1838, Axis axis (Erxleben, 1777), Rusa unicolor (Kerr, 1792), Rucervus duvaucelii (G.Cuvier, 1823), Alces alces (Linnaeus, 1758), Rangifer tarandus (Linnaeus, 1758), Odocoileus hemionus (Rafinesque, 1817), Odocoileus virginianus (Zimmermann, 1780), Pudu puda (Molina, 1782), Mazama americana (Erxleben, 1777), Antilocapra americana (Ord, 1815), Okapia johnstoni (P.L.Sclater, 1901), Giraffa camelopardalis (Linnaeus, 1758), Camelus dromedarius Linnaeus, 1758, Camelus bactrianus Linnaeus, 1758, Lama glama (Linnaeus, 1758), Diceros bicornis (Linnaeus, 1758), Ceratotherium simum (Burchell, 1817), Rhinoceros unicornis Linnaeus, 1758, Tapirus pinchaque (Roulin, 1829), Tapirus terrestris (Linnaeus, 1758), Equus grevyi Oustalet, 1882, Equus caballus Linnaeus, 1758, Equus asinus Linnaeus, 1758, Equus zebra Linnaeus, 1758, Paranyctimene raptor Tate, 1942, Cynopterus brachyotis (Müller, 1838), Macroglossus minimus (E.Geoffroy, 1810), Syconycteris australis (Peters, 1867), Dobsonia praedatrix K.Andersen, 1909, Dobsonia minor (Dobson, 1879), Dobsonia moluccensis (Quoy & Gaimard, 1830), Eonycteris spelaea (Dobson, 1871), Rousettus amplexicaudatus (E.Geoffroy, 1810), Pteropus scapulatus Peters, 1862, Pteropus giganteus (Brünnich, 1782), Pteropus poliocephalus Temminck, 1825, Pteropus hypomelanus Temminck, 1853, Pteropus voeltzkowi Matschie, 1909, Pteropus pumilus Miller, 1910, Pteropus rodricensis Dobson, 1878, Pteropus vampyrus (Linnaeus, 1758), Melonycteris melanops Dobson, 1877, Nyctimene cyclotis K.Andersen, 1910, Nyctimene albiventer (Gray, 1863), Rhinolophus ferrumequinum (Schreber, 1774), Rhinonicteris aurantia (Gray, 1845), Hipposideros galeritus Cantor, 1846, Macroderma gigas (Dobson, 1880), Pteronotus parnellii (Gray, 1843), Pteronotus personatus (Wagner, 1843), Pteronotus quadridens (Gundlach, 1840), Pteronotus davyi Gray, 1838, Noctilio leporinus (Linnaeus, 1758), Noctilio albiventris Desmarest, 1818, Rhinophylla pumilio Peters, 1865, Carollia perspicillata (Linnaeus, 1758), Sturnira lilium (E.Geoffroy, 1810), Sturnira erythromos (Tschudi, 1844), Artibeus concolor Peters, 1865, Artibeus lituratus (Olfers, 1818), Artibeus hirsutus K.Andersen, 1906, Platyrrhinus lineatus (E.Geoffroy, 1810), Uroderma bilobatum Peters, 1866, Chrotopterus auritus (Peters, 1856), Tonatia bidens (Spix, 1823), Phyllostomus hastatus (Pallas, 1767), Anoura caudifer (E.Geoffroy, 1818), Anoura latidens Handley, 1984, Monophyllus redmani Leach, 1821, Leptonycteris curasoae Miller, 1900, Glossophaga soricina (Pallas, 1766), Glossophaga longirostris Miller, 1898, Choeroniscus godmani (Thomas, 1903), Macrotus californicus Baird, 1858, Diphylla ecaudata Spix, 1823, Desmodus rotundus (E.Geoffroy, 1810), Diaemus youngi (Jentink, 1893), Mormoops megalophylla (Peters, 1864), Tadarida brasiliensis (I.Geoffroy, 1824), Molossus molossus (Pallas, 1766), Eumops perotis (Schinz, 1821), Peropteryx macrotis (Wagner, 1843), Saccopteryx bilineata (Temminck, 1838), Myotis myotis (Borkhausen, 1797), Myotis yumanensis (H.Allen, 1864), Tylonycteris robustula Thomas, 1915, Chalinolobus gouldii (Gray, 1841), Antrozous pallidus (LeConte, 1856), Eptesicus fuscus (Palisot de Beauvois, 1796), Natalus tumidirostris Miller, 1900, Histiotus velatus (I.Geoffroy, 1824), Nyctophilus timoriensis (E.Geoffroy, 1806), Nyctophilus geoffroyi Leach, 1821, Eidolon helvum (Kerr, 1792), Manis crassicaudata É.Geoffroy Saint-Hilaire, 1803, Manis javanica Desmarest, 1822, Manis tricuspis Rafinesque, 1821, Manis tetradactyla Linnaeus, 1766, Manis pentadactyla Linnaeus, 1758, Cerdocyon thous (Linnaeus, 1766), Cuon alpinus (Pallas, 1811), Speothos venaticus (Lund, 1842), Lycaon pictus (Temminck, 1820), Chrysocyon brachyurus (Illiger, 1815), Otocyon megalotis (Desmarest, 1822), Lycalopex culpaeus (Molina, 1782), Canis mesomelas Schreber, 1775, Canis lupus Linnaeus, 1758, Canis latrans Say, 1823, Urocyon cinereoargenteus (Schreber, 1775), Urocyon littoralis (Baird, 1858), Vulpes velox (Say, 1823), Vulpes lagopus (Linnaeus, 1758), Vulpes vulpes (Linnaeus, 1758), Vulpes zerda (Zimmermann, 1780), Ailuropoda melanoleuca (David, 1869), Tremarctos ornatus (F.G.Cuvier, 1825), Melursus ursinus (Shaw, 1791), Helarctos malayanus (Raffles, 1821), Ursus thibetanus G, Ursus americanus Pallas, 1780, Ursus arctos Linnaeus, 1758, Ursus maritimus Phipps, 1774, Odobenus rosmarus (Linnaeus, 1758), Callorhinus ursinus (Linnaeus, 1758), Neophoca cinerea (Péron, 1816), Zalophus californianus (Lesson, 1828), Eumetopias jubatus (Schreber, 1776), Arctocephalus pusillus (Schreber, 1775), Arctocephalus forsteri (Lesson, 1828), Mirounga leonina (Linnaeus, 1758), Mirounga angustirostris (Gill, 1866), Hydrurga leptonyx (de Blainville, 1820), Leptonychotes weddellii (Lesson, 1826), Erignathus barbatus (Erxleben, 1777), Halichoerus grypus (Fabricius, 1791), Phoca vitulina Linnaeus, 1758, Mephitis mephitis (Schreber, 1776), Spilogale putorius (Linnaeus, 1758), Ailurus fulgens F.G.Cuvier, 1825, Taxidea taxus (Schreber, 1777), Mellivora capensis (Schreber, 1776), Eira barbara (Linnaeus, 1758), Martes pennanti (Erxleben, 1777), Gulo gulo (Linnaeus, 1758), Martes flavigula (Boddaert, 1785), Martes americana (Turton, 1806), Pteronura brasiliensis Zimmermann, 1780, Lontra canadensis (Schreber, 1777), Enhydra lutris (Linnaeus, 1758), Hydrictis maculicollis (Lichtenstein, 1835), Aonyx capensis (Schinz, 1821), Lutra lutra (Linnaeus, 1758), Mustela frenata Lichtenstein, 1831, Mustela erminea Linnaeus, 1758, Mustela sibirica Pallas, 1773, Mustela nigripes (Audubon & Bachman, 1851), Mustela putorius Linnaeus, 1758, Mustela nivalis Linnaeus, 1766, Poecilogale albinucha (Gray, 1864), Potos flavus (Schreber, 1774), Procyon lotor (Linnaeus, 1758), Bassariscus astutus (Lichtenstein, 1830), Bassariscus sumichrasti (Saussure, 1860), Nasua narica (Linnaeus, 1766), Nasua nasua (Linnaeus, 1766), Nandinia binotata (Gray, 1830), Arctogalidia trivirgata (Gray, 1832), Arctictis binturong (Raffles, 1821), Paguma larvata (C.E.H.Smith, 1827), Paradoxurus hermaphroditus (Pallas, 1777), Hemigalus derbyanus (Gray, 1837), Genetta genetta (Linnaeus, 1758), Genetta tigrina (Schreber, 1776), Crocuta crocuta (Erxleben, 1777), Hyaena hyaena (Linnaeus, 1758), Suricata suricatta (Schreber, 1776), Helogale parvula (Sundevall, 1847), Herpestes javanicus (É.Geoffroy Saint-Hilaire, 1818), Crossarchus obscurus F.G.Cuvier, 1825, Galerella sanguinea (Rüppell, 1835), Fossa fossana (Müller, 1776), Cryptoprocta ferox Bennett, 1833, Mungotictis decemlineata (Grandidier, 1867), Lynx rufus (Schreber, 1777), Lynx canadensis Kerr, 1792, Lynx lynx (Linnaeus, 1758), Felis chaus Schreber, 1777, Felis nigripes Burchell, 1824, Felis silvestris Schreber, 1777, Felis margarita Loche, 1858, Prionailurus bengalensis (Kerr, 1792), Prionailurus viverrinus (Bennett, 1833), Acinonyx jubatus (Schreber, 1775), Puma concolor (Linnaeus, 1771), Leopardus geoffroyi (d'Orbigny & Gervais, 1844), Leopardus colocolo (Molina, 1782), Leopardus wiedii (Schinz, 1821), Leopardus pardalis (Linnaeus, 1758), Leptailurus serval (Schreber, 1776), Caracal caracal (Schreber, 1776), Catopuma temminckii (Vigors & Horsfield, 1827), Neofelis nebulosa (Griffith, 1821), Panthera pardus (Linnaeus, 1758), Panthera onca (Linnaeus, 1758), Panthera leo (Linnaeus, 1758), Panthera tigris (Linnaeus, 1758), Uncia uncia (Schreber, 1775), Notiosorex crawfordi (Coues, 1877), Cryptotis parva (Say, 1823), Blarina carolinensis (Bachman, 1837), Blarina brevicauda (Say, 1823), Sorex palustris Richardson, 1828, Sorex cinereus Kerr, 1792, Sorex coronatus Millet, 1828, Sorex alpinus Schinz, 1837, Sorex minutus Linnaeus, 1766, Sorex vagrans Baird, 1857, Neomys fodiens (Pennant, 1771), Crocidura hildegardeae Thomas, 1904, Crocidura olivieri (Lesson, 1827), Crocidura russula (Hermann, 1780), Crocidura viaria (I.Geoffroy Saint-Hilaire, 1834), Crocidura poensis (Fraser, 1843), Crocidura luna Dollman, 1910, Suncus etruscus (Savi, 1822), Suncus murinus (Linnaeus, 1766), Scalopus aquaticus (Linnaeus, 1758), Neurotrichus gibbsii (Baird, 1858), Condylura cristata (Linnaeus, 1758), Hemiechinus auritus (Gmelin, 1770), Atelerix albiventris (Wagner, 1841), Paraechinus aethiopicus (Ehrenberg, 1832), Erinaceus concolor Martin, 1838, Erinaceus europaeus Linnaeus, 1758, Hylomys suillus Müller, 1840, Echinosorex gymnura (Raffles, 1822), Oryctolagus cuniculus (Linnaeus, 1758), Brachylagus idahoensis (Merriam, 1891), Lepus timidus Linnaeus, 1758, Lepus arcticus Ross, 1819, Lepus alleni Mearns, 1890, Lepus californicus Gray, 1837, Lepus townsendii Bachman, 1839, Lepus americanus Erxleben, 1777, Sylvilagus floridanus (J.A.Allen, 1890), Sylvilagus audubonii (Baird, 1858), Ochotona curzoniae (Hodgson, 1858), Ochotona princeps (Richardson, 1828), Glis glis (Linnaeus, 1766), Graphiurus ocularis (Smith, 1829), Graphiurus murinus (Desmarest, 1822), Muscardinus avellanarius (Linnaeus, 1758), Aplodontia rufa (Rafinesque, 1817), Ratufa bicolor (Sparrman, 1778), Paraxerus palliatus (Peters, 1852), Paraxerus cepapi (A.Smith, 1836), Epixerus ebii (Temminck, 1853), Tamias minimus Bachman, 1839, Tamias merriami J.A.Allen, 1889, Tamias amoenus J.A.Allen, 1890, Tamias striatus (Linnaeus, 1758), Cynomys ludovicianus (Ord, 1815), Spermophilus dauricus Brandt, 1843, Spermophilus citellus (Linnaeus, 1766), Marmota monax (Linnaeus, 1758), Marmota flaviventris (Audubon & Bachman, 1841), Marmota caligata (Eschscholtz, 1829), Marmota vancouverensis Swarth, 1911, Ammospermophilus harrisii (Audubon & Bachman, 1854), Ammospermophilus leucurus (Merriam, 1889), Xerus princeps (Thomas, 1929), Xerus inauris (Zimmermann, 1780), Sundasciurus tenuis (Horsfield, 1824), Callosciurus notatus (Boddaert, 1785), Callosciurus prevostii (Desmarest, 1822), Callosciurus nigrovittatus (Horsfield, 1823), Glaucomys volans (Linnaeus, 1758), Sciurus aureogaster F.Cuvier, 1829, Sciurus niger Linnaeus, 1758, Sciurus carolinensis Gmelin, 1788, Sciurus variegatoides Ogilby, 1839, Sciurus vulgaris Linnaeus, 1758, Tamiasciurus hudsonicus (Erxleben, 1777), Hystrix cristata Linnaeus, 1758, Hystrix indica Kerr, 1792, Hystrix africaeaustralis Peters, 1852, Heterocephalus glaber Rüppell, 1842, Heliophobius argenteocinereus Peters, 1846, Cryptomys hottentotus (Lesson, 1826), Georychus capensis (Pallas, 1778), Bathyergus suillus (Schreber, 1782), Bathyergus janetta Thomas & Schwann, 1904, Coendou prehensilis (Linnaeus, 1758), Sphiggurus mexicanus (Kerr, 1792), Dolichotis salinicola Burmeister, 1876, Dolichotis patagonum (Zimmermann, 1780), Kerodon rupestris (Wied-Neuwied, 1820), Galea musteloides Meyen, 1833, Cavia porcellus (Linnaeus, 1758), Dasyprocta mexicana Saussure, 1860, Dasyprocta azarae Lichtenstein, 1823, Dasyprocta cristata (É.Geoffroy Saint-Hilaire, 1803), Dasyprocta punctata Gray, 1842, Dasyprocta leporina (Linnaeus, 1758), Myoprocta acouchy (Erxleben, 1777), Cuniculus paca (Linnaeus, 1766), Ctenomys opimus Wagner, 1848, Ctenomys fulvus Philippi, 1860, Ctenomys maulinus Philippi, 1872, Ctenomys talarum Thomas, 1898, Ctenomys australis Rusconi, 1934, Tympanoctomys barrerae (Lawrence, 1941), Octomys mimax Thomas, 1920, Octodontomys gliroides (Gervais & d'Orbigny, 1844), Spalacopus cyanus (Molina, 1782), Aconaemys fuscus (Waterhouse, 1842), Octodon degus (Molina, 1782), Thrichomys apereoides (Lund, 1839), Myocastor coypus (Molina, 1782), Proechimys semispinosus (Tomes, 1860), Capromys pilorides (Say, 1822), Dinomys branickii Peters, 1873, Lagostomus maximus (Desmarest, 1817), Lagidium viscacia (Molina, 1782), Chinchilla chinchilla (Lichtenstein, 1829), Chinchilla lanigera Bennett, 1829, Pedetes capensis (Forster, 1778), Napaeozapus insignis (Miller, 1891), Zapus hudsonius (Zimmermann, 1780), Zapus princeps J.A.Allen, 1893, Dipus sagitta (Pallas, 1773), Jaculus orientalis Erxleben, 1777, Jaculus jaculus (Linnaeus, 1758), Cannomys badius (Hodgson, 1841), Rhizomys sumatrensis (Raffles, 1821), Tachyoryctes splendens (Rüppell, 1835), Mystromys albicaudatus (A.Smith, 1834), Steatomys pratensis Peters, 1846, Saccostomus campestris Peters, 1846, Cricetomys emini Wroughton, 1910, Cricetomys gambianus Waterhouse, 1840, Hypogeomys antimena A.Grandidier, 1869, Phodopus sungorus (Pallas, 1773), Phodopus campbelli (Thomas, 1905), Mesocricetus auratus (Waterhouse, 1839), Cricetus cricetus (Linnaeus, 1758), Cricetulus migratorius (Pallas, 1773), Lemmiscus curtatus (Cope, 1868), Neofiber alleni True, 1884, Myopus schisticolor (Lilljeborg, 1844), Lasiopodomys brandtii (Radde, 1861), Microtus breweri (Baird, 1857), Microtus canicaudus Miller, 1897, Microtus longicaudus (Merriam, 1888), Microtus cabrerae Thomas, 1906, Microtus mexicanus (Saussure, 1861), Microtus ochrogaster (Wagner, 1842), Microtus agrestis (Linnaeus, 1761), Microtus xanthognathus (Leach, 1815), Microtus oeconomus (Pallas, 1776), Microtus pinetorum (Le Conte, 1830), Microtus californicus (Peale, 1848), Microtus pennsylvanicus (Ord, 1815), Microtus montanus (Peale, 1848), Microtus richardsoni (DeKay, 1842), Microtus arvalis (Pallas, 1779), Microtus guentheri (Danford & Alston, 1880), Arvicola amphibius (Linnaeus, 1758), Chionomys nivalis (Martins, 1842), Myodes californicus (Merriam, 1890), Myodes gapperi (Vigors, 1830), Ondatra zibethicus (Linnaeus, 1766), Phenacomys intermedius Merriam, 1889, Lemmus lemmus (Linnaeus, 1758), Lemmus sibiricus (Kerr, 1792), Dicrostonyx groenlandicus (Traill, 1823), Arborimus longicaudus (True, 1890), Ochrotomys nuttalli (Harlan, 1832), Baiomys taylori (Thomas, 1887), Scotinomys xerampelinus (Bangs, 1902), Scotinomys teguina (Alston, 1877), Peromyscus gossypinus (Le Conte, 1853), Peromyscus maniculatus (Wagner, 1845), Peromyscus truei (Shufeldt, 1885), Peromyscus megalops Merriam, 1898, Peromyscus leucopus (Rafinesque, 1818), Peromyscus polionotus (Wagner, 1843), Peromyscus californicus (Gambel, 1848), Peromyscus eremicus (Baird, 1857), Peromyscus crinitus (Merriam, 1891), Megadontomys thomasi (Merriam, 1898), Reithrodontomys megalotis (Baird, 1857), Neotoma lepida Thomas, 1893, Neotoma fuscipes Baird, 1857, Neotoma albigula Hartley, 1894, Neotoma cinerea (Ord, 1815), Eligmodontia typus F.Cuvier, 1837, Sigmodon hispidus Say & Ord, 1825, Oligoryzomys longicaudatus (Bennett, 1832), Akodon azarae (Fischer, 1829), Oxymycterus roberti Thomas, 1901, Chelemys macronyx (Thomas, 1894), Abrothrix longipilis (Waterhouse, 1837), Calomys musculinus (Thomas, 1913), Graomys griseoflavus (Waterhouse, 1837), Phyllotis darwini (Waterhouse, 1837), Auliscomys boliviensis (Waterhouse, 1846), Phyllotis xanthopygus (Waterhouse, 1837), Acomys cahirinus (É.Geoffroy, 1803), Acomys russatus (Wagner, 1840), Acomys subspinosus (Waterhouse, 1838), Acomys spinosissimus Peters, 1852, Sekeetamys calurus (Thomas, 1892), Desmodillus auricularis (A.Smith, 1834), Meriones unguiculatus (Milne-Edwards, 1867), Meriones crassus Sundevall, 1842, Meriones hurrianae Jordon, 1867, Gerbillus nanus Blanford, 1875, Gerbillus pyramidum (É.Geoffroy, 1803), Gerbillus andersoni de Winton, 1902, Gerbillus pusillus Peters, 1878, Gerbillus gerbillus (Olivier, 1800), Dipodillus dasyurus (Wagner, 1842), Dipodillus campestris (Levaillant, 1857), Gerbilliscus afra (Gray, 1830), Gerbilliscus leucogaster (Peters, 1852), Gerbillurus paeba (A.Smith, 1836), Gerbillurus tytonis (Bauer & Niethammer, 1960), Gerbillurus setzeri (Schlitter, 1973), Gerbillurus vallinus (Thomas, 1918), Myotomys unisulcatus (F.Cuvier, 1829), Myotomys sloggetti (Thomas, 1902), Thallomys paedulcus (Sundevall, 1846), Hydromys chrysogaster É.Geoffroy, 1804, Conilurus penicillatus (Gould, 1842), Uromys caudimaculatus (Krefft, 1867), Notomys cervinus (Gould, 1853), Notomys alexis Thomas, 1922, Pseudomys gracilicaudatus (Gould, 1845), Pseudomys hermannsburgensis (Waite, 1896), Chiropodomys gliroides (Blyth, 1856), Mastomys natalensis (A.Smith, 1834), Mus minutoides A.Smith, 1834, Mus musculus Linnaeus, 1758, Mus spretus Lataste, 1883, Mus macedonicus Petrov & Ruzic, 1983, Apodemus chevrieri (Milne-Edwards, 1868), Apodemus speciosus (Temminck, 1845), Apodemus sylvaticus (Linnaeus, 1758), Apodemus flavicollis (Melchior, 1834), Apodemus mystacinus (Danford & Alston, 1877), Lemniscomys griselda (Thomas, 1904), Rhabdomys pumilio (Sparrman, 1784), Micaelamys namaquensis (A.Smith, 1834), Otomys irroratus (Brants, 1827), Parotomys brantsii (A.Smith, 1834), Micromys minutus (Pallas, 1771), Sundamys muelleri (Jentink, 1879), Rattus fuscipes (Waterhouse, 1839), Rattus colletti (Thomas, 1904), Rattus annandalei (Bonhote, 1903), Rattus lutreolus (J.E.Gray, 1841), Rattus norvegicus (Berkenhout, 1769), Rattus villosissimus (Waite, 1898), Rattus tiomanicus (Miller, 1900), Niviventer cremoriventer (Miller, 1900), Leopoldamys sabanus (Thomas, 1887), Maxomys rajah (Thomas, 1894), Maxomys surifer (Miller, 1900), Phloeomys pallidus Nehring, 1890, Castor canadensis Kuhl, 1820, Dipodomys deserti Stephens, 1887, Dipodomys merriami Mearns, 1890, Dipodomys ordii Woodhouse, 1853, Dipodomys panamintinus (Merriam, 1894), Dipodomys microps (Merriam, 1904), Dipodomys agilis Gambel, 1848, Dipodomys spectabilis Merriam, 1890, Microdipodops megacephalus Merriam, 1891, Microdipodops pallidus Merriam, 1901, Liomys irroratus (Gray, 1868), Heteromys anomalus (Thompson, 1815), Heteromys desmarestianus Gray, 1868, Liomys salvini (Thomas, 1893), Chaetodipus baileyi (Merriam, 1894), Chaetodipus fallax (Merriam, 1889), Chaetodipus californicus (Merriam, 1889), Chaetodipus intermedius (Merriam, 1889), Chaetodipus hispidus (Baird, 1858), Perognathus longimembris (Coues, 1875), Perognathus flavus Baird, 1855, Geomys pinetis Rafinesque, 1817, Geomys bursarius (Shaw, 1800), Thomomys umbrinus (Richardson, 1829), Thomomys bottae (Eydoux & Gervais, 1836), Thomomys talpoides (Richardson, 1828), Ptilocercus lowii Gray, 1848, Tupaia minor Günther, 1876, Tupaia glis (Diard, 1820), Tupaia tana Raffles, 1821, Tupaia belangeri (Wagner, 1841), Galago moholi A.Smith, 1836, Galago senegalensis É.Geoffroy Saint-Hilaire, 1796, Otolemur garnettii (Ogilby, 1838), Otolemur crassicaudatus (É.Geoffroy Saint-Hilaire, 1812), Perodicticus potto (Müller, 1766), Loris tardigradus (Linnaeus, 1758), Nycticebus pygmaeus Bonhote, 1907, Nycticebus coucang (Boddaert, 1785), Daubentonia madagascariensis (Gmelin, 1788), Propithecus tattersalli Simons, 1988, Propithecus verreauxi Grandidier, 1867, Cheirogaleus medius É.Geoffroy Saint-Hilaire, 1812, Mirza coquereli (A.Grandidier, 1867), Microcebus murinus (J.F.Miller, 1777), Varecia variegata (Kerr, 1792), Eulemur rubriventer (I.Geoffroy Saint-Hilaire, 1850), Eulemur coronatus (Gray, 1842), Eulemur macaco (Linnaeus, 1766), Eulemur mongoz (Linnaeus, 1766), Eulemur fulvus (É.Geoffroy Saint-Hilaire, 1796), Lemur catta Linnaeus, 1758, Hapalemur griseus (Link, 1795), Ateles paniscus (Linnaeus, 1758), Ateles belzebuth É.Geoffroy Saint-Hilaire, 1806, Ateles fusciceps Gray, 1866, Ateles geoffroyi Kuhl, 1820, Alouatta caraya (Humboldt, 1812), Cebus capucinus (Linnaeus, 1758), Cebus olivaceus Schomburgk, 1848, Saimiri boliviensis (I.Geoffroy Saint-Hilaire & de Blainville, 1834), Saimiri sciureus (Linnaeus, 1758), Saimiri oerstedii (Reinhardt, 1872), Callimico goeldii (Thomas, 1904), Callithrix geoffroyi (Humboldt, 1812), Callithrix jacchus (Linnaeus, 1758), Callithrix penicillata (É.Geoffroy Saint-Hilaire, 1812), Leontopithecus chrysomelas (Kuhl, 1820), Leontopithecus chrysopygus (Mikan, 1823), Leontopithecus rosalia (Linnaeus, 1766), Saguinus bicolor (Spix, 1823), Saguinus midas (Linnaeus, 1758), Saguinus geoffroyi (Pucheran, 1845), Saguinus oedipus (Linnaeus, 1758), Saguinus imperator (Goeldi, 1907), Saguinus mystax (Spix, 1823), Aotus vociferans (Spix, 1823), Aotus trivirgatus (Humboldt, 1811), Aotus lemurinus I.Geoffroy Saint-Hilaire, 1843, Aotus nancymaae Hershkovitz, 1983, Aotus nigriceps Dollman, 1909, Pithecia pithecia (Linnaeus, 1766), Symphalangus syndactylus (Raffles, 1821), Hylobates pileatus Gray, 1861, Hylobates lar (Linnaeus, 1771), Hylobates moloch (Audebert, 1798), Hylobates agilis F.Cuvier, 1821, Hylobates muelleri Martin, 1841, Nomascus concolor (Harlan, 1826), Nomascus leucogenys (Ogilby, 1840), Nomascus gabriellae (Thomas, 1909), Pongo pygmaeus (Linnaeus, 1760), Gorilla gorilla (Savage, 1847), Homo sapiens Linnaeus, 1758, Pan troglodytes (Blumenbach, 1775), Pan paniscus Schwarz, 1929, Colobus angolensis Sclater, 1860, Colobus polykomos (Zimmermann, 1780), Colobus guereza Rüppell, 1835, Pygathrix nemaeus (Linnaeus, 1771), Nasalis larvatus (van Wurmb, 1787), Semnopithecus entellus (Dufresne, 1797), Trachypithecus francoisi (de Pousargues, 1898), Trachypithecus auratus (É.Geoffroy Saint-Hilaire, 1812), Trachypithecus cristatus (Raffles, 1821), Trachypithecus obscurus (Reid, 1837), Mandrillus sphinx (Linnaeus, 1758), Mandrillus leucophaeus (F.Cuvier, 1807), Cercocebus torquatus (Kerr, 1792), Cercocebus galeritus Peters, 1879, Cercocebus agilis A.Milne-Edwards, 1886, Theropithecus gelada (Rüppell, 1835), Papio hamadryas (Linnaeus, 1758), Lophocebus albigena (Gray, 1850), Macaca radiata (É.Geoffroy Saint-Hilaire, 1812), Macaca thibetana (A.Milne-Edwards, 1870), Macaca fascicularis (Raffles, 1821), Macaca mulatta (Zimmermann, 1780), Macaca fuscata (Blyth, 1875), Macaca silenus (Linnaeus, 1758), Macaca nemestrina (Linnaeus, 1766), Macaca nigra (Desmarest, 1822), Miopithecus talapoin (Schreber, 1774), Allenopithecus nigroviridis (Pocock, 1907), Erythrocebus patas (Schreber, 1774), Cercopithecus campbelli Waterhouse, 1838, Chlorocebus aethiops (Linnaeus, 1758), Cercopithecus hamlyni Pocock, 1907, Cercopithecus neglectus Schlegel, 1876, Cercopithecus mona (Schreber, 1775), Cercopithecus pogonias Bennett, 1833, Cercopithecus wolfi Meyer, 1891, Cercopithecus diana (Linnaeus, 1758), Cercopithecus petaurista (Schreber, 1774), Cercopithecus ascanius (Audebert, 1799), Cercopithecus mitis Wolf, 1822, Cercopithecus nictitans (Linnaeus, 1766), Notoryctes caurinus Thomas, 1920, Macrotis lagotis (Reid, 1837), Perameles nasuta É.Geoffroy Saint-Hilaire, 1804, Perameles gunnii Gray, 1838, Isoodon macrourus (Gould, 1842), Isoodon obesulus (Shaw, 1797), Isoodon auratus (Ramsay, 1887), Echymipera kalubu (Fischer, 1829), Echymipera rufescens (Peters & Doria, 1875), Myrmecobius fasciatus Waterhouse, 1836, Planigale maculata (Gould, 1851), Planigale tenuirostris Troughton, 1928, Planigale gilesi Aitken, 1972, Antechinomys laniger (Gould, 1856), Sminthopsis murina (Waterhouse, 1838), Sminthopsis crassicaudata (Gould, 1844), Sminthopsis macroura (Gould, 1845), Ningaui yvonnae Kitchener, Stoddart & Henry, 1983, Phascogale tapoatafa (Meyer, 1793), Antechinus swainsonii (Waterhouse, 1840), Antechinus stuartii Macleay, 1841, Antechinus flavipes (Waterhouse, 1838), Pseudantechinus macdonnellensis (Spencer, 1896), Sarcophilus harrisii (Boitard, 1841), Dasyurus hallucatus Gould, 1842, Dasyurus maculatus (Kerr, 1792), Dasyurus viverrinus (Shaw, 1800), Dasyurus geoffroii Gould, 1841, Dasycercus cristicauda (Krefft, 1867), Dasyuroides byrnei Spencer, 1896, Tarsipes rostratus Gervais & Verreaux, 1842, Petaurus breviceps Waterhouse, 1838, Dactylopsila trivirgata Gray, 1858, Pseudocheirus peregrinus (Boddaert, 1785), Petauroides volans (Kerr, 1792), Acrobates pygmaeus (Shaw, 1793), Aepyprymnus rufescens (Gray, 1837), Petrogale xanthopus Gray, 1854, Setonix brachyurus (Quoy & Gaimard, 1830), Wallabia bicolor (Desmarest, 1804), Macropus robustus Gould, 1840, Macropus rufus (Desmarest, 1822), Macropus fuliginosus (Desmarest, 1817), Macropus giganteus Shaw, 1790, Macropus parma Waterhouse, 1846, Macropus eugenii (Desmarest, 1817), Macropus agilis (Gould, 1841), Macropus rufogriseus (Desmarest, 1817), Lagorchestes conspicillatus Gould, 1841, Dendrolagus inustus Müller, 1840, Dendrolagus goodfellowi Thomas, 1908, Dendrolagus matschiei Forster & Rothschild, 1907, Bettongia gaimardi (Desmarest, 1822), Bettongia penicillata Gray, 1837, Potorous tridactylus (Kerr, 1792), Trichosurus vulpecula (Kerr, 1792), Phalanger gymnotis Peters & Doria, 1875, Spilocuscus maculatus (É.Geoffroy Saint-Hilaire, 1803), Burramys parvus Broom, 1896, Cercartetus nanus (Desmarest, 1818), Cercartetus concinnus (Gould, 1845), Cercartetus lepidus (Thomas, 1888), Phascolarctos cinereus (Goldfuss, 1817), Vombatus ursinus (Shaw, 1800), Lasiorhinus latifrons (Owen, 1845), Caluromys derbianus (Waterhouse, 1841), Caluromys lanatus (Olfers, 1818), Lutreolina crassicaudata (Desmarest, 1804), Chironectes minimus (Zimmermann, 1780), Metachirus nudicaudatus (É.Geoffroy Saint-Hilaire, 1803), Monodelphis domestica (Wagner, 1842), Monodelphis brevicaudata (Erxleben, 1777), Didelphis virginiana Kerr, 1792, Didelphis albiventris Lund, 1840, Didelphis marsupialis Linnaeus, 1758, Gracilinanus microtarsus (Wagner, 1842), Philander opossum (Linnaeus, 1758))" ] } The dataset includes 14129650 records from 4476 constituent datasets: 2 records from Mauernacker (Wettsaasen). 35 records from Happywhale - Killer Whale in Arctic Ocean. 3 records from FFH-Gebiet Klosterwasser/Burkau. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Hubert GUIMIER. 1 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Programme Ecoscope: données d'observations des écosystèmes marins exploités (Réunion). 19 records from Plan de gestion 2017 - 2021 de la Réserve Naturelle Régionale d'Errota Handia (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par piège photographique) réalisées par le CEN Nouvelle-Aquitaine. 136 records from Réseau Loup - Lynx ONCFS - Lynx 2005 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 15 records from Feral Pigs - Sightings and Cull records - 2017-2018. 2707 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 24 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 329 records from NMML Small Cetacean Aerial Survey 1997. 24 records from Données DREAL Centre-Val de Loire - Faune - 2018. 83 records from Registros biológicos de predios promocionados como Reservas Naturales de la Sociedad Civil-RNSC en el Cañón de Amaime, municipio El Cerrito, Valle del Cauca, Colombia.. 184 records from Fauna presente en el proyecto Minera de Cobre Quebradona, municipio de Jericó. 21 records from Species of plants, fungi and animals from separate territories of Podesinnia. 2 records from Freiburger GEO-Tag der Artenvielfalt. 1 records from Ostfriesland. 96 records from Observatoire des sites majeurs - LEYRE - Inventaire et suivi Loutre d'Europe. 201 records from Fototrampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 853 records from Réserves Naturelles de France (RNF) - RNF - Données du Parc Naturel Régional du Vercors. 11 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna” (Mamíferos no voladores). 55 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2016. 424 records from SWFSC Marine Mammal Survey, ORCAWALE 2008, Cruise 1635. 30 records from Occurrences of Threatened Species included in the Third Edition of the Red Data Book of the Komi Republic (Russia). 1734 records from MMS O2 1982-1984. 40 records from AFTT JAX Aerial Survey -Right side- 2012-2013. 40 records from South Australia's Sea Lions as Ocean Observers (aggregated per 1-degree cell). 1 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 35 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 33023 records from National Dormouse Database (NDD). 394 records from Colección de Mamíferos del Museo de Historia Natural de la Universidad de la Amazonia (UAM-M). 127 records from Plan de gestion 2017 - 2021 de la Réserve Naturelle Régionale d'Errota Handia (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 41 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 2 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 16 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de TEISSEDRE BERTRAND. 37 records from MMS Seabird Ecology Study 1985. 86680 records from UAM Mammal Collection (Arctos). 324 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 41 records from Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010. 23 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste PARISOT FRANCK provenant de la base de donnée du SINP Île-de-France CETTIA. 35 records from SILENE-FAUNE-PACA - Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 6 records from Occurrence of mammalia relicts at site Climauti II. 42 records from ONCFS Réseau Ours brun - Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 1 records from Waldi-Weiher. 1 records from Inventaire du site Natura 2000 FR7401107 "Landes des Monédières" - Inventaire chiroptères. 102 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 215 records from Invasive Non-Native Species, Outer Hebrides. 2 records from Gewann Krampf (Heilbronn). 89 records from Norfolk/VA Beach MINEX Vessel Surveys. 27 records from AFTT JAX Aerial Survey -Left side- 2014. 8 records from (Table 1) Proportion of Toxoplasma gondii seropositive arctic foxes (Alopex lagopus) by age group and geographic area. 30 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 1999. 1 records from Synthèse de la Répartition des populations de cerf élaphe en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 4 records from Projet Vianne : construction et exploitation de canalisations de transport de gaz naturel sur les communes de Thouars-sur-Garonne, Feugarolles, Vianne, Lavardac et Nérac (Lot-et-Garonne) - Données faune-flore recueillies dans le cadre de l'étude d'impact. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2010 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1 records from Enquête sur 3 mammifères protégés : le Muscardin, le Campagnol amphibie et la Crossope aquatique - Données mammifères Phase 2 récoltées par LPO France. 1 records from Happywhale - Harbor Porpoise in Arctic Ocean. 40876 records from CLICNAT- Base de données naturaliste picarde - CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 1508 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 1 records from Inventaires de la faune exotique envahissante - Sciences participatives sur les espèces animales introduites (EEE-FIF). 25 records from Gestion de sites - Données ANA - CEN Ariège sur la gestion conservatoire (occurences de taxons). 1247 records from Ibaraki Nature Museum, Mammals collection. 6480 records from Lajitietokeskus/FinBIF - Notebook, general observations. 1126 records from Occurrences de mammifères du Groupe Mammalogique Normand (GMN) - Occurrence de Carnivores du Groupe Mammalogique Normand (GMN). 508 records from Northern elephant seals post-molting 2017 (aggregated per 1-degree cell). 8 records from Occurrence of mammalia relicts at site Icoana. 512 records from SILENE-FAUNE-PACA - Ecosphère_2017_12_18. 4 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de David SOULET. 1623 records from Estonian Museum of Natural History Department of Zoology. 47 records from Fermanagh Flora. 2 records from Royal Belgian Institute of Natural Sciences Bird collection. 9 records from Wald am Schloss Wittgenstein Bad Laasphe. 6045 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 1 records from Stadtpark Prinzengarten (Sigmaringen). 1 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste JOSSERAND oriane provenant de la base de donnée du SINP Île-de-France CETTIA. 46 records from Inventarios de la biodiversidad en el piedemonte subandino de Yopal. 67 records from Biodiversidad asociada al proyecto Conexión Urabá - Nueva Colonia - Apartadó a 110 kV, Antioquia. 4 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de François BRETON. 363 records from Lothian Wildlife Information Centre Secret Garden Survey. 2288 records from Atlas / Observatoire des Mammifères de Bretagne - Données Ongulés et Lagomorphes en Bretagne de 2000 à 2016. 3 records from KYMA boat-based surveys in Thyrrhenian Sea and Ionian Sea. 1 records from Schulhofuntersuchung Thomas-Mann-OS. 19 records from Happywhale - Fin Whale in Arctic Ocean. 78 records from UNCW Aerial Survey 1998-1999. 67 records from Plan de gestion 2019 - 2023 de la Réserve Naturelle Régionale de l’Étang de Chourroumillas (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 594 records from Atlas of Bats from Continental Portugal 2013. 738 records from Données Faune Base SIRFF - FNE Centre-Val de Loire - Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 2 records from Plan de gestion 2019 - 2023 du site des Grottes de Sare (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Nouvelle-Aquitaine. 55 records from Caracterización y monitoreo de fauna silvestre en el área de influencia directa de Hidrocasanare- Yopal del 2014 a 2017. 21094 records from Western Australian Museum provider for OZCAM. 163 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 690 records from Finds of small mammals in the Kharkiv region. 576 records from Deforestación y fragmentación del hábitat: consecuencias ecológicas sobre la fauna de mamíferos de la selva tropical estacional. 1441 records from NRW Regional Data: South East Wales Non-sensitive species. 329 records from UNCW Marine Mammal Sightings 2001. 112 records from SWFSC Marine Mammal Survey, STAR-LITE 2007, Cruise 1634. 35 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Joana PERRODIN. 1 records from Waldstück am Schullandheim Bad Bederkesa. 1348 records from Osteology collections of World Museum, National Museums Liverpool. 22 records from Occurrence of mammalia relicts at site Goyet Cave 3. 103 records from Inventaire de la faune vertébrés du Parc national du Mercantour - Inventaire de la faune de vertébrés du Parc national du Mercantour. 2 records from FERME ÉOLIENNE DE BLANZAY - Chiroptères blanzay printemps 2016. 7 records from Occurrence of mammalia relicts at site Jaskinia Niedwiedzia. 412 records from Colección Mastozoológica de la Universidad Industrial de Santander. 433 records from Registro de murciélagos del Cañón del Chicamocha, Santander (2013 - 2014). 90 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 104 records from Réseau Loup - Lynx ONCFS - Lynx 2002 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 2 records from Données naturalistes de BONCHE Jérôme. 4 records from Happywhale - Spinner Dolphin in North Atlantic Ocean. 408 records from NatureShare. 7 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes du Comité départemental de l'Essonne (CODEP91) de la Fédération Française d'Etudes et de Sports Sous-Marins. 82711 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 2 records from Naturerlebnisraum Koppelsberg. 3591 records from Arctic Species Trend Index (ASTI) : Marine. 2 records from UCM Vertebrate Observations Collection (Arctos). 157 records from Ohio Wesleyan University Mammal Specimens (Arctos). 2 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Dylan FOURNIER. 4 records from Occurrence of mammalia relicts at site Adler Cave xx. 1187 records from MMS Marine Mammal Survey, PNW 1989-1990. 218 records from Field Museum of Natural History (Action) Mammals Sightings. 1 records from Plan de gestion multi-site 2020 - 2024 des lagunes d'Hourtin (33) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 6403 records from United Kingdom National Whale Stranding Database 1913-2008. 671 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Christophe CHAMBOLLE. 7001 records from Données de l'atlas des Mammifères sauvages de Midi-Pyrénées (données agrégées à la maille de 10km). 4 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 16 records from Occurrence of mammalia relicts at site Istalloskö. 1 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 1 records from Base BOMBINA du Parc Naturel régional Lorraine - Natura 2000 Vallée de la Seille. 4 records from Umgebung der Gesamtschule Winterhude (Hamburg). 2 records from Ferme éolienne du Mont-Louis - Données écologiques de la ferme éolienne de Mont-Louis. 14 records from Local BioBlitz Challenge 2013. 2557 records from SILENE-FAUNE-PACA - Amis_des_Marais_du_Vigueirat_2017_12_18. 33 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Arnaud HORELLOU. 111 records from Réseau Loup - Lynx ONCFS - Lynx 2016 présence Occasionnelle Mailles_10km_LAEA Réseau Loup-Lynx ONCFS. 269 records from HRC SCC Aerial-Based Monitoring Survey February 2010. 7545 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 4 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de THÉVENOT Jessica. 15 records from Occurrence of mammalia relicts at site Biedermann. 1 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Inventaire chiroptérologique dans les Chataigneraies du PNRPL - Inventaire bioaccoustique et capture au filet de chiroptères en verger à châtaignes 2019. 4 records from Plan de gestion du Marais du Logit - Inventaire opportuniste Faune. 1 records from Unna-Mühlhausen, Wiesen. 414 records from Données collectées dans de cadre de la première cartographie des périmètres des ZNIEFF continentales de type 1 et 2 de Mayotte. 125 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Occasionnelle du Loup en 2009. 3 records from RSPB Lochwinnoch incidental species records. 2701 records from niek_2022. 172 records from AMAPPS Northeast Aerial Cruise Summer 2011. 4978 records from Whale catches in the Southern Ocean. 41 records from Réseau Loup - Lynx ONCFS - Lynx 1999 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 388 records from Loup 2016 présence régulière communale (réseau Loup-Lynx ONCFS). 3 records from Plan régional d'actions en faveur des odonates (PRAO) : 4ème phase (2019 - 2020) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine (Étude Leucorrhines). 1726 records from Natural Resources Wales Regional Data : Mid-Wales. 9 records from Jeu de données convention Saint-Gobain Distribution Bâtiment France -SPN-MNHN - Données Saint-Gobain Distribution Bâtiment France. 11 records from Données biodiversité Ferme éolienne de St Mard. 13 records from Occurrence of mammalia relicts at site Wildenscheuer Cave. 34 records from River Biologists' Database (EPA). 1 records from Selztal bei Friesenheim. 6 records from Occurrence of mammalia relicts at site Brühl 1. 47 records from Great Eastern Ranges - Slopes to Summit. 13069 records from UCM Mammal Collection (Arctos). 8780 records from Data collected on citizen science web portal www.ornitho.cat. 58 records from Mamíferos medianos y grandes observados en la expedición al Río Apaporis - Proyecto Colombia BIO. 2115 records from Swedish Bird Survey: Fixed routes (Standardrutterna). 26 records from SEFSC Gomex Shelf 1998. 45 records from Mammals (GNHM-MM). 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Pascal REVAULT. 730 records from The BCT/MTUK Bats & Roadside Mammals Survey. 848 records from Données supplémentaires Atlas des Mammifères marins. 6 records from Occurrence of mammalia relicts at site Ochtendung. 685 records from Activités du CEN Nouvelle-Aquitaine anciennement CEN Limousin - Regroupement de données du CEN Nouvelle-Aquitaine (ex CEN Limousin). 6875 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Arnoul MATEO. 11 records from Occurrence of mammalia relicts at site Ochoz Cave. 443 records from Oceanic Society's Marine Mammal Sightings in Belize 1992 - 2011. 9 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 4 records from Waldstück Bremerhagen LK Bio Kl. 12. 12 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaire des mammifères du Parc de la Haute-Île (93). 16 records from Wild boar culled on the National Forest Estate Scotland 2018-19. 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 1 records from Überschwemmungsgebiet der Wied. 14 records from Plan de gestion de la Réserve Naturelle Régionale de la Massonne - Inventaire de données. 1910 records from Captive Primate Specimens of Japan Monkey Centre. 14 records from Tejidos colectados en la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia.. 4 records from Biodiversity of the Desna river valley and its tributaries. 1 records from Bannwald Burghauser Forst. 2 records from Données naturalistes de EL ATTAR SOFI OUMAYMA. 11 records from New England Aquarium Harbor Porpoise Tracking (aggregated per 1-degree cell). 36 records from TRANSMED cétacés - Données Cétacés Transmed. 29 records from Données du Groupe d'étude des Cétacés de Méditerranée - Observations de cétacés en Méditerranée par le Groupe d'étude des Cétacés de Méditerranée de 2012 à 2017. 14 records from Données du Comité Départemental de Protection de la Nature et de l'Environnement de Loir-et-Cher (CDPNE) - Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 366 records from UCSC Elephant Seals (aggregated per 1-degree cell). 1 records from HRC Koa Kai Marine Species Monitoring Vessel Surveys November 2010. 3 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Florent HERVOUET. 3 records from Ferme éolienne d'Arnac sur dourdou - Faune. 20 records from Réseau Loup - Lynx ONCFS - Lynx 1990 présence Régulière Mailles_10km_LAEA Réseau Loup-Lynx ONCFS. 119 records from Collection des mammifères d'Auvergne. 15 records from HRC SCC Aerial-based Transect Surveys February 2011. 88 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 6 records from Données de Shell Exploration and Production France - Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France. 1 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1 records from Waldsee. 69 records from AMAPPS Southeast Aerial Cruise Fall 2016. 2230 records from Distribution des Cétacés et Siréniens dans les eaux de Nouvelle-Calédonie. 49 records from Occurrence of mammalia relicts at site Pod hradem. 1 records from SILENE-FAUNE-PACA - GERECO_Environnement_2017_12_18. 9 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 72 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 28 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 73 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 6 records from Programme les sentinelles du climat - effets du changement climatique sur la biodiversité en région Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 1 records from Projet de parc éolien sur la commune d'Envronville - Données faune terrestre. 130741 records from Happywhale - Humpback Whale in North Pacific Ocean. 2 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" site de La Beute (Tosse). 17 records from CNAC/Coleccion Nacional de Acaros. 2 records from Carnivores of Syria. 10 records from Cetacean occurrence off the west central Portugal coast from boat-based surveys 2007-2008. 39 records from Collections of Bioclass, school #179, Moscow. 2178 records from BLM CETAP AIR Sightings. 27 records from Réseau Loup - Lynx ONCFS - Lynx 1988 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 5 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaires "Espaces Naturels Sensibles" du Luy (Saugnac-et-Cambran). 37639 records from Mammalia (Luomus). 722 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2016. 165 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Chiron François provenant de la base de donnée du SINP Île-de-France CETTIA. 20 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 43 records from Plan de gestion 2015-2020 de la tourbière de Passeben - Inventaire et suivi Faune. 50 records from SEUS Right Whale EWS Aerial Surveys 2017-18. 1 records from Inventaire participatif Chauves souris du littoral - Données du GCA saisies sur Faune Aquitaine. 5 records from Elaboration du DOCOB du site Natura 2000 ‘Zones humides de Moliets, la Prade et Moïsan’ (FR7200717) - Inventaire et regroupement de données Natura 2000. 2516 records from NMU Mammal Collection (Arctos). 1 records from Condamine Alliance. 202 records from Small rodents in mountain birch forest 2002-2016. 1 records from Schanzenanlage Bergham. 4 records from St Andrews BioBlitz 2015. 1 records from Données espèces - Expertise IQE 64. 12 records from Monitoreo del oso andino en el Parque Nacional Natural Cordillera de los Picachos - julio y agosto de 2018. 13047 records from CMNH Mammals. 162 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Occasionnelle du Loup en 2011. 728 records from Steller sea lion (Eumetopias jubatus) counts and haulout locations British Columbia. 30 records from Mesures compensatoires sur des projets de Collectivités territoriales - Données CEN L-R Compensation collectivités. 243 records from AMAPPS Northeast Aerial Cruise Summer 2010. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 49 records from EDP Foz Tua: Bat Habitats - Complementary Studies [2010]. 24 records from HRC CRC Small Vessel-Based Monitoring Surveys July 2006. 218 records from Murciélagos observados en la expedición al Río Apaporis - Proyecto Colombia BIO. 20 records from Marsabit Ecosystem Inventory Surveys 2014. 19 records from checklist-of-mammals-of-liwonde-national-park. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Adeline AIRD. 51 records from Colección de Zoología Universidad Icesi: Mamíferos. 48 records from Southern Highlands Nature Map. 26 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 349 records from SWFSC Marine Mammal Survey, CalCurCEAS 2014, Cruise 1647. 958 records from Fauna species from the Sectoral Plan of the Natura 2000 (Polygons). 17 records from Manx Wildlife Trust - Records. 2 records from Bulau. 1753 records from TOPP Summary of SSM-derived Telemetry. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 1596 records from Happywhale - Humpback Whale in Arctic Ocean. 29 records from UNCW Hatteras Aerial Survey - Right side - 2015. 9 records from Conventions de partenariat sur les terrains militaires d'Occitanie - Données convention de gestion CEN MP - autorités du camp militaire (Camp du Causse). 40 records from Murciélagos de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 116 records from Acquario di Genova, Delfini Metropolitani Project, cetacean sightings 2001-2009. 5 records from HRC USWEX Aerial-Based Monitoring Surveys 2007. 49 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 243 records from Cetacean distribution around Mayotte Island. 37 records from Visual and genetic surveys for odontocete cetaceans in American Samoa 2003-06. 4 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 24 records from Occurrence of mammalia relicts at site Felsställe. 16 records from Parc éolien la Croix de la Mérotte - Données Biodiversité Etude d'impact parc éolien Croix de la Mérotte. 4159 records from NWTRC JP04 Aerial Surveys 2014-2015. 411 records from University of Michigan Museum of Paleontology - Vertebrates. 4 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaire faunistique de l'ENS des Parc des berges de Seine. 3 records from Programmes de connaissance sur les zones humides d'Occitanie - Données ANA - CEN Ariège sur les zones humides (occurences de taxons). 9764 records from Queensland Museum provider for OZCAM. 583 records from SCANS II cetacean sightings on primary platform of vessel surveys 2005. 1 records from Plan de gestion 2019 - 2023 du site des Grottes de Sare (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur LAFAGE Denis. 3 records from Spießwoogtal / Königsbruch (Fischbach). 78 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Occasionnelle du Loup en 2001. 3 records from Données espèces - Expertise IPE 93. 16 records from List of invasive or harmful alien species in Wallis and Futuna Territory. 341 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 175 records from Inventario de Fauna Vertebrada de la Reserva Forestal Protectora Regional de los Cañones de los Ríos Melcocho y Santo Domingo. 1 records from Herpetofauna and other animals registered within Rzhyshchiv city amalgamated territorieal community (CATC) (Kyiv region) in 2021. 269 records from NMML Killer Whale Vessel, Kodiak Island, 1993. 4 records from Ortelsbruch - Hangmoor bei Morbach. 2673 records from Ongulés de Guyane. Synthèse réalisée pour la Liste rouge. 80 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Olivier ESCUDER. 18 records from Données d'expertise convention GTM Bâtiment et le Service du patrimoine naturel du MNHN. 2 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Céline HOUGH. 3 records from Artenvielfalt der Nordsee - Helgoland. 203 records from Happywhale - Leopard seal in South Atlantic Ocean. 717 records from Redland City Council Citizen Science Portal. 31395 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 967 records from T. L. Hankinson Vertebrate Museum (EMU) Mammal Collection. 30908 records from WildNet - Queensland Wildlife Data. 1 records from JAX SEASWITI Aerial Monitoring 2010. 2 records from Zielbach (Töll). 1 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 70 records from ONCFS Réseau Ours brun - Ours 2010 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 177 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 2 records from Projet du parc éolien de la Voie des Prêtres 2 - Mammifères inventoriés de manière fortuite en 2017. 657 records from (UTC) University of Tennessee Mammals Collection. 56 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste PROVOST romain provenant de la base de donnée du SINP Île-de-France CETTIA. 35039 records from University of Michigan Museum of Zoology, Division of Mammals. 2 records from Schulgelände Kranich-Gymnasium (Salzgitter). 47 records from Caracterización de Fauna del Banco de Hábitat del Bosque Seco Tropical Antioquia de Terrasos. 4 records from Données biodiversité projet éolien des Navarros. 364 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" de Gaouchey et de Garlande (LUXEY). 6 records from Occurrence of mammalia relicts at site Groß-Rohrheim. 15387 records from DMNS Mammal Collection (Arctos). 3 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Quentin ROME. 35 records from Occurrence of mammalia relicts at site Rejtek 1. 24 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Vindras Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 31 records from HRC CRC Small Vessel-Based Monitoring Surveys April-May 2009. 65 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 1 records from Ensembe de diagnostics écologiques sur la commune de Cabanac-et-Villagrains-Gironde. - Inventaire opportunistes Faune. 1 records from Artenvielfalt auf dem Schulgelände. 6 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Iris PRINET. 1 records from Notice de gestion 2014 - 2018 de la bande de servitude de l'artère Girland (40) de Teréga mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 8 records from National Museum of Natural Science. 24 records from Occurrence of mammalia relicts at site Vogelherd/Lonetal. 118 records from SWFSC Marine Mammal Survey, PODS 1992, Cruise 1467. 4 records from Plan de gestion 2013 - 2018 du site des Coteaux de Las Hies (64) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 158 records from AMAPPS Northeast Shipboard Cruise Summer 2011. 2 records from Results of a recent bat survey in Upper Myanmar including new records from the Kachin forests. 5 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Gourlin Benjamin provenant de la base de donnée du SINP Île-de-France CETTIA. 18 records from Elaboration du DOCOB du site Natura 2000 ‘Zones humides de l'arrière dune du Marensin’ (FR7200718) - Inventaire et regroupement de données Natura 2000. 7 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Laurence Beauchamp. 2 records from Ferme Eolienne de la Région de Guise - Données écologiques de la ferme éolienne de Guise. 393 records from MCP-Mamiferos - Coleção de Mamíferos. 2 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Bruno OGER. 1 records from Collection Gilles Becquet (BOUM). 108 records from Chronicle of Nature - Phenology of Mammals of Surhanskiy State Nature Reserve. 272 records from SOCAL Marine Mammal Aerial Monitoring 2008-2009. 6 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du Syndicat de la Vallée de l'Orge Aval (SIVOA). 24 records from Occurrence of mammalia relicts at site Felsställe. 9 records from Red de varamientos de Euskadi - Sistema de Información de la Naturaleza de Euskadi. 11 records from Projet éolien des Chagnasses - Données brutes de biodiversité. 68 records from Alien Species in Poland - Animals. 22 records from Occurrence database of native plants and animals of south-central Chile. 1 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 35 records from AFTT JAX Aerial Survey -Left side- 2012-2013. 25 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 11473 records from Swiss National Bat Databank: Regional Coordination Western Switzerland (CCO). 34 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 7788 records from UF Florida Museum of Natural History Mammals. 1672 records from Happywhale - Humpback Whale in Indian Ocean. 956 records from Cascadia Research Collective Hawaii OASIS project whale and dolphin sightings. 130 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 2008. 16 records from Zambian Bat Collections Worldwide. 9 records from Occurrence of species of animals listed in the Red Book of Ukraine on the territory of the "Medobory" nature reserve and in the adjacent territories in 2021. 30217 records from Fichier communal des ongulés. 4 records from Projet éolien de Saint-Barbant - Autre faune. 36 records from Réseau Loup - Lynx ONCFS - Lynx 1992 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 38 records from Programmes de connaissance sur les milieux secs d'Occitanie - Données CEN M-P Milieux secs. 24 records from UNCW Norfolk Canyon Aerial Survey - Right side - 2015. 658 records from SILENE-FAUNE-PACA - DDT05_2017_12_18. 1 records from Naturpark Kottenforst-Ville 15.6.09. 368 records from HogWatch Scotland Project - West European hedgehog records between 2019 and 2021. 20 records from The Belgica 121 expedition to the Western Antarctic Peninsula: a high resolution biodiversity census. 1 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" de Bas-Rouge (SAINT-MICHEL-ESCALUS). 6 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 43 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 49 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Branger Fabien provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Données espèces - Expertise IPE 79. 53336 records from NBIS Records to December 2016. 12 records from Projet de parc éolien des Portes du Nivernais - Données d'inventaires écologiques faube-flore. 3 records from Finchingfield Brook historic river corridor surveys. 30 records from Cetacean coordinated transborder monitoring using ferries as platforms of observation off Tunisia 2013-2014 - Atutax. 1676 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2012. 12 records from South American Antarctic Marine Biodiversity Literature. 2 records from Projet éolien dit du Château - Données écologiques du projet éolien du Château. 5 records from Happywhale - Spinner Dolphin in North Pacific Ocean. 3 records from SILENE-FAUNE-PACA - Métropole_Nice_Côte_d'Azur_2017_12_18. 1 records from Données espèces - Expertise IPE 70. 40 records from ONCFS Réseau Ours brun - Ours 2005 présence Régulière Mailles 10km LAEA Réseau Ours brun ONCFS. 24 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 273 records from Programme d’acquisition et de valorisation de données naturalistes BioObs - Observations naturalistes des Amis de BioObs.. 840 records from Happywhale - Leopard seal in Southern Ocean. 288 records from SOCAL FZN4 Marine Mammal Aerial Monitoring 2013. 88 records from Actions Natura 2000 - Données invertébrés dans le cadre de la participation au réseau N2000. 27318 records from Diversité et répartition des mammifères non-volants d'Auvergne (Groupe Mammalogique d'Auvergne - LPO Auvergne) - Données de Carnivores collectées ou analysées par le Groupe Mammalogique d’Auvergne.. 2 records from Steinbruch Mainz-Weisenau, 2. Jahr. 4 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Mammifères remarquables - Inventaire non standardisé - LPO74. 2212 records from HSU Wildlife Mammals. 133 records from SWFSC Marine Mammal Survey, CADDIS 1995, Cruise 1601. 5 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaires tous taxons réalisés pendant l'année 2014 le long de la Petite Ceinture à Paris. 17 records from NCSM Vertebrate Paleontology Collection. 11 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 36 records from ONCFS Réseau Ours brun - Ours 2002 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 5 records from Cetaceans in the Southern Indian Ocean 2004. 15 records from Census of animals species through Benin from 2011 to 2019. 2 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 24 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 61 records from DUML vessel-based photo-id and biopsy surveys for proposed JAX USWTR site 2012-2015. 1 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 46 records from SEFSC Mid-Atlantic Tursiops Survey, 1995 (1). 264 records from Population research on small rodents (Rodentia) and shrews (Soricidae) in Steinkjer Municipality – Norway; 1996 - 2017 based on systematic catches with ordinary mouse traps in traplines. 1 records from Teich Berlin Wuhlheide. 75718 records from Natural History Museum (London) Collection Specimens. 3 records from Diagnostic écologique et élaboration d'une notice de gestion (prairies humides et calcaires) sur la commune de Monflanquin (47) menés entre 2017 et 2022 par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 1 records from Occurrence of mammalia relicts at site Raagelund. 59 records from ONCFS Réseau Ours brun - Ours 2007 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 89 records from Occurrence of mammalia relicts at site Grotte Scladina. 3 records from Projet de port de plaisance de Brétignolles sur Mer - Mammifères - Inventaire non protocolé. 5 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from Jordal. 3 records from Projet photovoltaïque au sol de Marigny - Terre Neuve (79) - Volet "autre faune" - projet photovoltaïque de Marigny - Terre Neuve (79). 1 records from Förderzentrum Schmölln. 35 records from Mammals collected and illustrated by the Baudin Expedition to Australia and Timor (1800 - 1804): A review of the current taxonomy of specimens in the Muséum national d’Histoire naturelle de Paris and the illustrations in the Muséum d’Histoire naturelle du Havre. 4 records from Parc éolien de la Société d’Exploitation du Parc Eolien des Noues à Blacy (51) - Inventaire non protocolé des mammifères terrestres. 79 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 277 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 12 records from WADFW PSAMP S1996. 2 records from Centrale solaire Zac de l'Empereur - Etude d'Impact Données Faune/Flore. 1 records from Artenvielfalt auf Zollverein. 1 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Jarry Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Entomological Collection. 1336 records from Tanami Pipeline Project Records. 2 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 81 records from Données Association Évasion tropicale (AET) - Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 6 records from Projet photovoltaïque de la Grenette - Données brutes biodiv Chabrillan EOLFI. 30998 records from Elephant Seal Sightings, Macquarie Island. 10 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 224 records from Vertebrate specimens of Jyväskylä University Museum. 16 records from Hazel Dormouse in Ireland. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de SANDY BARBERIS. 126 records from HRC USWEX Aerial-based Shoreline Surveys February and March 2011. 118 records from Review of otter status along the River Dee and its tributaries. 56 records from USWTR JAX Aerial Survey -Right side- 2009-2010. 371 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 9 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Danten Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 62 records from Mammalogie ZMK. 1 records from Suivi et inventaire de la réserve naturelle de Saucats - La Brède - Données récoltées dans le cadre du suivi de la réserve. 91 records from Données du Sanctuaire AGOA issues de l'agence de Aires marines protégées - Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 1471 records from Long-term monitoring of primate, bird, and ungulate populations 2010-2020 for protected area management, Keo Seima Wildlife Sanctuary, Cambodia. 163 records from Data from Defra Family Organisations supplied to Staffordshire Ecological Record. 42 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, méxico. 5 records from UNCW PAX Aerial Survey - Left side - 2017. 12 records from Inventario de Murciélagos Buena Vista, Jaramá, Yopal, Casanare. 11 records from SILENE-FAUNE-PACA - Thibaut_LACOMBE_2017_12_18. 2 records from Etude Chiroptères du domaine de Peyssac - Etude Chiroptères de Peyssac. 119 records from Données faune ZNIEFF de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS. 266 records from Phenological Center - Mammals (Arkhangelsk). 24854 records from NatureServe Network Species Occurrence Data. 124 records from Small mammal species list 08. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 16372 records from University of Nebraska State Museum Mammals Collection. 2 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Matthieu BERRONEAU. 11 records from Global Register of Introduced and Invasive Species - Alaska, United States. 3 records from Tejidos de armadillo (Dasypus novemcinctus) colectados en el marco del Proyecto: Filogeografía, estructura poblacional y diversidad genética de armadillos. 6 records from Sightings for REMUS Sonar Test Event - July 2013. 9 records from Cetaceans sighted off the west coast of the South Island, New Zealand, Summer 1970. 212 records from Small Wild Cats of Eurasia. 128 records from Réseau Loup - Lynx ONCFS - Lynx 2014 présence Occasionnelle Mailles_10km_LAEA Réseau Loup-Lynx ONCFS. 42 records from ONCFS Réseau Ours brun - Ours 2008 présence Régulière Mailles_10km_LAEA Réseau Ours brun ONCFS. 3928 records from Allied Humpback Whale Catalogue, 1976 - 2003. 1 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Projet DYNAMIQUES - Suivi de la biodiversité sur le Plateau de Saclay élargi. 5 records from Truppenübungsplatz Panzerkaserne Böblingen. 11 records from SNI California Sea Lions 2014 (aggregated per 1-degree cell). 3 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Communauté_de_Communes_CIANS-VAR_2017_12_18. 148 records from Regroupement d'études et d'inventaires - Données faunistiques en attente de rattachement. 14286 records from Données de la plateforme régionale SINP DREAL Bourgogne - Données de l'Observatoire de la Faune de Bourgogne. 30 records from Occurrence of mammalia relicts at site Einhornhöhle. 9755 records from NEON Biorepository Mammal Collection (Hair Samples). 2 records from Regroupement d'études et inventaires - Régulation espèces invasives. 11 records from Occurrence of mammalia relicts at site Große Ofnethöhle. 12 records from Occurrence of mammalia relicts at site Lespezi-Lutarie. 1 records from Plan de gestion 2017 - 2021 du site des neuf fontaines et de l'airial du Larousse (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 7 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Jean-Patrick Le Duc. 3300 records from Protocole de recensement des collisions entre la faune sauvage et les véhicules de la Direction interdépartementale des routes de l'Ouest - Données de mortalité de la faune par collision avec les véhicules sur le réseau routier de la DIR Ouest de 2018 à 2019. 23 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 398 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 5 records from SILENE-FAUNE-PACA - If_Ecologie_Conseil_2017_12_18. 3 records from Some zoological observations in Kherson region of Ukraine. 12 records from Gestion du site des prés-salés Est de la Teste-de-Buch du conservatoire du littoral et de sites naturels aux alentours - Données opportunistes faune. 35 records from Cetacean observations in Avacha Gulf 2005-2009. 53 records from Leopard and Weddell seal program 1999/2002. 248 records from Orca observations from the shores of Macquarie Island. 81 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Ségolène FAUSTEN. 3506 records from Colección Mastozoológica del IADIZA - CCT CONICET Mendoza: IADIZA-CMI. 6 records from Rango, comportamiento, tamaño de población y conservación de felinos en el Volcán de Colima. 122156 records from Artportalen (Swedish Species Observation System). 11 records from Mamíferos voladores de San Andrés y Providencia - Expedición Sea Flower Plus 2021. 366 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 3 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la Ville de Colombes provenant de la base de donnée du SINP Île-de-France CETTIA. 76 records from Regroupement d'études et inventaires - Suivi quotidien. 4 records from Bernhardsthal. 516 records from Alnitak-Alnilam Cetaceans and sea turtles surveys off Southern Spain. 24 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste KERYER Guy provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Etude écologique du Parc des Lilas (94). 2 records from Centrale photovoltaïque de Sainte-Julie - données environnementales de Sainte-Julie. 124 records from NMML Gulf of Alaska marine mammal survey 2003. 1948 records from Mammal assemblages recorded by camera traps inside and outside the evacuation zone of the Fukushima Daiichi Nuclear Power Plant accident. 301 records from Northern elephant seals post-breeding 2015 (aggregated per 1-degree cell). 55 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur Pratz Jean-Louis. 161 records from SWFSC Marine Mammal Survey, MOPS 1987, Cruise 1081. 70 records from AFTT Hatteras Aerial Survey -Left side- 2012-2013. 7 records from Happywhale - Polar Bear in Arctic Ocean. 85 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Occasionnelle du Loup en 2004. 6 records from Demande de renouvellement et d'extension d'autorisation de carrière au titre de la rubrique 2510 des ICPE - Carrière de Villemanoche (89) - Donnees biodiversite carriere Villemanoche 181210. 290 records from Estonian lynx samples. 416 records from National System of Protected Areas in Poland - Animals. 111 records from Зимние маршрутные учеты в заказнике «Березовский» (Ханты-Мансийский Автономный Округ). 12 records from Mastofauna presentes en la ciénaga de Guineo, Riosucio, Chocó. 1 records from Plan de gestion 2016 - 2020 du site du vallon du Clamondé (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 12 records from Occurrence of mammalia relicts at site Rusenschloß. 159 records from AMAPPS Northeast Aerial Cruise Summer 2016. 2 records from WADFW PSAMP S1992. 67 records from Fauna species from the Sectoral Plan of the Natura 2000 (Points). 15 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 6 records from South Lanarkshire peatland records 2013. 9 records from NEFSC Mid-Atlantic Marine Mammal Abundance Survey 2004. 14 records from Conventions de partenariat sur les terrains militaires d'Occitanie - Données convention de gestion CEN MP - autorités du camp militaire (Camp de Ger). 2 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste GAUTHIER Nicolas provenant de la base de donnée du SINP Île-de-France CETTIA. 24 records from ONCFS Réseau Ours brun - Ours 2016 présence Régulière Mailles 10km LAEA Réseau Ours brun ONCFS. 10 records from Happywhale - Gray Whale in Arctic Ocean. 53 records from Transferts SI Faune - Données naturalistes opportunistes de Cedric DEVILLEGER. 24787 records from Monitoring scheme of birds and mammals that are visiting bird feeders during winter. 1 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 3153 records from MICA - Muskrat occurrences collected by RATO in East Flanders, Belgium. 74 records from NMML Harbor Porpoise Vessel Survey, SE Alaska, Fall 1991. 1 records from Condrictios del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 112 records from Florida Museum Environmental Archaeology Baptizing Springs Zooarchaeological Data. 35 records from Données opportunistes collectées par les agents du Département des Landes. 5 records from Données CEN L-R RHOMEO. 5 records from Mammifères des mangroves et des zones humides du sud Togo. 8 records from Occurrence of mammalia relicts at site Großes Schulerloch. 7 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 2 records from CRC HRC Shore-based Surveys KB11 2013-2015. 1255 records from National Whale and Dolphin Sightings and Strandings Database. 4 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 825 records from Restauración y conservación de Isla Guadalupe. 110 records from Plan de sauvegarde des chiroptères sur la partie aquitaine du PNRPL - Inventaire et suivi Chiroptère. 16 records from HRC CRC Small Vessel-Based Monitoring Surveys August-September 2011. 96 records from Colección Mastozoológica-Museo de Historia Natural Unillanos. 267 records from Biodiversidad asociada al gasoducto Paiva-Caracolí. 6 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" du Plata (SORE). 205 records from Wild boar sightings held by Andy Riches. 18 records from Community Foundation for Ireland Records. 31 records from ONCFS Réseau Ours brun - Ours 2005 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 54 records from Regroupement d'études et d'inventaires - Inventaire Chiroptères collectées par contact en main. 41020 records from The Danish Environmental Portal, species and habitats-database "Danmarks Miljøportals Naturdatabase". 18 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Clémentine Gand. 2 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Franck UTEAU. 3 records from Argentina–Chile National Geographic Pristine Seas Expedition To The Antarctic Peninsula - Deep Sea Cam Data. 32 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 3 records from Occurrence of mammalia relicts at site Meiendorf. 13 records from Occurrence of mammalia relicts at site Remetehegy. 84 records from Point counts of breeding terrestrial birds. 11 records from SEFSC GoMMAPPS Vessel Survey 2018 Summer. 8 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 1 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 29 records from Projet éolien en mer de Dieppe Le Tréport - Mammifères marins - transects en mer. 25 records from Plan de gestion multi-sites à Chiroptères mené par le CEN Aquitaine depuis 2008 - Observations de chiroptères (suivi par dénombrement) réalisées par le CEN Nouvelle-Aquitaine. 8332 records from Scotland Otter Survey Database. 1 records from Plan de gestion 2018 - 2022 du site de Saulié (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 2 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Mikaël PAILLET. 6 records from Données du Parc National de la Guadeloupe - Données de type contact en Guadeloupe. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Charles BRESSON. 1 records from Inventaire en continu de la ZNIEFF 'Prairies Du Loubet Et Du Tolzac' - 720020107 - Prairies du Loubet et du Tolzac - Inventaire Oiseaux, Amphibiens & Reptiles opportunistes. 3 records from Bizzenbachtal (Wehrheim/Taunus). 21 records from BOEM Sperm Whale Seismic Study (SWSS) S-Tag cetacean sightings 2002-2004. 9 records from Projet éolien de Plestan II - Volet chiroptère/étude en altitude. 881 records from Manx Biological Recording Partnership UNVERIFIED Isle of Man records between 14/02/2017 and 05/09/2019. 2 records from Family Emballonuridae (Sheath-tailed Bats). 17 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Occasionnelle du Loup en 1997. 43 records from SEFSC Mid-Atlantic Tursiops Survey, 1995 3. 338 records from Inventario multitaxonómico del ANP Médanos de Samalayuca. 3125 records from Programme CarNET B (Cartographie Nationale des Enjeux Territorialisés de Biodiversité Remarquable) - Carnet B Lorraine. 1 records from Naturalis Biodiversity Center (NL) - Pisces. 2 records from Inventaire en continu de la ZNIEFF 'Lettes de Baine de Lédasse' - 720030126 - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 556 records from La ballena jorobada, Megaptera novaeangliae, en la Península de Baja California Sur, México. 8 records from Projet de construction d'une centrale photovltaïque au sol-Exoudun - Données Exoudun. 18 records from Killer whales occurrences in Venezuelan waters 1982-2008. 11 records from Mamíferos de la Ecoreserva Predio Isla IV (Cantagallo, Bolívar) - Proyecto FIBRAS. 724 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 284 records from Seasearch Marine Surveys in England. 2 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Annales de la Société Linnéenne de Maine-et-Loire. 59 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Données de Mammifères marins dans les TAAF et autres territoires issues de la bibliographies. Compte cardobs 1007 (Trudelle). 373 records from Mammal records captured from Licence Returns submitted to Natural Resources Wales. 3 records from projet photovoltaique l'epine - Inventaire des mammifères pour le projet de parc photovoltaïque de l'Epine. 2 records from e-Valley, le plus grand parc e-logistique d'Europe - Mammifères terrestres - Inventaire non standardisé. 3 records from PROJET DE CENTRALE PHOTOVOLTAÏQUE SAINTE ANNE LA ROCHE SUR YON - Inventaire espèces presente sur site. 72 records from Monitoreo participativo de fauna presente en Bosque Seco de los departamentos de Bolivar, Huila y La guajira. 5 records from Élaboration du 1er plan de gestion du site de l’Étang de Chourroumillas (64) mené par le CEN Aquitaine en 2003 - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 2 records from Projet de carrière - Ravine du Trou - Saint-Leu (974) - Inventaires de la biodiversité marine. 92 records from Occurrence of mammalia relicts at site Raj Cave. 6754 records from NeoWild Brownsberg Nature Park Camera trap Monitoring 2016-2017. 16 records from Programmes d'Atlas de la biodiversité communale (ABC) - Atlas de la Biodiversité Communale sur le territoire du Parc National des Pyrénées - Données du CEN MP. 21 records from NEFSC Deepwater Marine Mammal 2002. 4 records from Quarrendorfer Landschaftsschutzgebiet. 106 records from Programa Poseidon - Citizen Science Project Results. 18 records from SILENE-FAUNE-PACA - Parc_Naturel_Régional_des_Préalpes_d'Azur_2017_12_18. 4087 records from BLM CETAP OPP Sightings. 5 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Pauline BALDUCCI. 220 records from CalCOFI marine mammal surveys 2004-2008 - on effort. 15 records from La collection des préparations zoologiques (BOUM). 3 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste LELARDOUX LOIC provenant de la base de donnée du SINP Île-de-France CETTIA. 16 records from MoJ BioBlitz August 2018. 1604 records from University of Tartu Natural History Museum and Botanical Garden Zooloogical Collections. 3096 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 5 records from Kaouk - The Trailer Park Steller Sea Lion (aggregated per 1-degree cell). 51 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 2 records from Parc photovoltaïque sur la comme de Préfontaines - Parc photovoltaïque sur la commune de Préfontaines. 2945 records from Porpoise Observation Database (NRM). 29 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Atlas de la biodiversité de Bordeaux Métropole 2015 - Recensement des chiroptères 2012/2014 - Atlas de la biodiversité de Bordeaux Métropole. 30 records from Mamíferos pequeños asociados a las cuencas abastecedoras del embalse La Fe en el departamento de Antioquia. 6 records from Mammal type specimens in the Macleay Collections, University of Sydney. 126 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases - Iberian Wolf [spotlight counts] - [2010-2014]. 19 records from Shrews of Poland. 275 records from Aerial Oil Spill Response Survey 1994-1997. 5665 records from The Dolphin Project. 3 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 28 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from Caracterización de vertebrados terrestres en el Cerro Guadalupe, municipio de Manzanares. 905 records from Registro de vertebrados durante el fototrampeo del convenio 027 - 2014 CVC - Panthera. 4 records from Umgebung der Gesamtschule Hamburg-Winterhude. 23 records from Arizona State University Vertebrate Tissue Collection. 6 records from BUND - Dassower See (Lübeck/Dassow). 988 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 13 records from Mamíferos de la Ecoreserva CPF Cupiagua (Aguazul, Casanare) - Proyecto FIBRAS. 2 records from Marine sites, habitats and species data collected during the BioMar survey of Ireland.. 26 records from Mamíferos colectados en la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 30 records from ONCFS Réseau Ours brun - Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 11 records from Arthur Chapman Observations. 12 records from Schulzentrum "Parc Hosingen". 2 records from Cuxhavener Küstenheiden. 2 records from Signalements d'espèces exotiques envahissantes collectés par le Groupe espèces invasives de La Réunion (GEIR) sur la plateforme "web-GEIR" - Signalement d'espèces exotiques envahissantes - Export mai 2018 de la base de données du GEIR. 18211 records from Hatikka.fi observations. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de AUNEAU Florent. 30290 records from Données du parc national de la Vanoise. 50 records from inatura - Erlebnis Naturschau Dornbirn. 696 records from Galiano Island BC Canada Marine Zoology 1893–2021. 13 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 605 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Otter [2010-2014]. 45 records from Images and observations of mostly edible plants in Stephen Barstow’s Edible Garden in Norway, taken between 2005 and 2014. 3891 records from LSUMZ Mammal Tissues. 2 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Verna Eric provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 1 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 1 records from Projet de parc éolien de la Croix Guingal, sur la commune de Derval (44 590) - Croix Guingal - chiro - transit printanier 2014. 10 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 1 records from Projets de suivis faunes association Environat - suivi odonates environat. 3 records from Happywhale - Bowhead in North Pacific Ocean. 203 records from Mesures compensatoires routes nationales - données compensation routes nationales - ex région M-P. 21 records from SEFSC GoMex Oceanic 2000. 7 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" de Marthe (SAINT-SEVER-MONTGAILLARD). 1 records from Synthèse de la Répartition des populations de chamois en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 2 records from Plan de gestion 2007 - 2011 du site des tourbières de Mées (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 724 records from Line transect censuses of breeding birds. 3 records from Projet éolien de Berceronne - Données brutes Chiroptères. 15 records from HRC SCC Vessel-Based Monitoring Surveys February 2010. 212 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 22 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Julien-Laferrière Didier provenant de la base de donnée du SINP Île-de-France CETTIA. 25 records from Données de Aquasearch et Dauphin Passion - Données Mammifères marins Aquasearch - Dauphin Passion. 6 records from HRC RIMPAC Vessel-Based Monitoring Surveys 2008. 1 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Ville_de_Fréjus_2017_12_18. 510 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 184 records from WTSWW Data: All Taxa (West Wales). 537 records from CRESLI marine mammal observations from whale watch cruises 2000-2019. 1 records from Données espèces - Expertise IPE 10. 28143 records from South Australian Museum Australia provider for OZCAM. 2 records from Plan de gestion 2008 - 2012 du site de la Butte de la Lot (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 22 records from Occurrence of mammalia relicts at site Spitalhöhle. 26 records from Seasearch Marine Surveys in Ireland. 5 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 87379 records from DOF - Observations from the Danish Ornithological Society. 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 1 records from Base BOMBINA du Parc Naturel régional Lorraine - Flore Bord de route/CG55 - Parc Naturel régional Lorraine. 10 records from Projet éolien de Lan Vraz - Volet avifaune, chiroptère (étude au sol), flore. 1 records from DASSH Data Archive Centre volunteer survey data. 342 records from NEFSC Aerial Circle-Back Abundance Survey 2006. 28 records from A New Mormoopid Bat From The Oligocene (Whitneyan And Early Arikareean) Of Florida, And Phylogenetic Relationships Of The Major Clades Of Mormoopidae (Mammalia: Chiroptera). 1 records from Unter hellen Zinnen und finsteren Grotten. 20999 records from HBRG Vertebrates (not Badger) Dataset. 863 records from UNCW Marine Mammal Aerial Surveys 2006-2007. 1 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Grégory Patek. 3 records from Gomex Sperm Whale Survey 2000. 6 records from Base BOMBINA du Parc Naturel régional Lorraine - Modernisation des ZNIEFF du PnrL. 8 records from Occurrence of mammalia relicts at site Niederlehme. 632 records from NMML 2002-2010 Bering Sea Shelf Cetacean Survey. 55 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Jean-Christophe BARTOLUCCI. 1 records from Coastal and Marine Species Database. 11 records from Convention Fédération française de golf - MNHN 2016-2019. 130 records from SWFSC Marine Mammal Survey, STAR 1998, Cruise 1611. 1211 records from Tasmanian Museum and Art Gallery provider for OZCAM. 615 records from TTRS Mammals. 3 records from Données espèces - Expertise IPE 23. 66 records from Occurrence of mammalia relicts at site Veternica. 5 records from HRC Aerial Surveys Aug 20-22 2013. 3 records from Happywhale - Short-finned Pilot Whale in South Atlantic Ocean. 24 records from GEO-Hauptveranstaltung in "Wildtierland". 25 records from Inventario Murciélagos Finca Naranjito, Aracal, Yopal, Casanare. 2747 records from CSUC Vertebrate Collection. 92 records from Marybio Foundation marine mammal shipboard sightings in Bahia San Antonio, Patagonia 2008-2010. 5 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste DESCHATRE Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 37772 records from Données naturalistes opportunistes Faune-France - Liste des espèces de la faune sauvage de la base de données naturalistes Faune-France 2018.. 13 records from HRC CRC Small Vessel-Based Monitoring Surveys December 2009. 2 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Fósseis (ZUFMS-FOS). 1295 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 45 records from Brown bear monitoring data from Deosai National Park. 16 records from DUML coastal surveys on the occurrence, distribution and density of marine mammals in Camp Lejeune 2010-2013. 1 records from Synthèse de la Répartition des populations de mouflon corse en 2011 (réseau Ongulés sauvages ONCFS-FNC-FDC). 534 records from Leopard Seal census, Heard Island 1987/88. 1 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Limagne Vincent provenant de la base de donnée du SINP Île-de-France CETTIA. 20 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 5 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 1 records from Occurrence of mammalia relicts at site High Furlong. 5 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Pierre-Yves GOURVIL. 6 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 70 records from Réseau Loup - Lynx ONCFS - Lynx 2004 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 360 records from Densidad poblacional para fauna medida por medio de cámaras trampa en los Valores Objeto de Conservación (VOC) del territorial Andes Occidentales. 24 records from Population research on small rodents (Rodentia) and shrews (Soricidae) in Steinkjer Municipality – Norway; 2018-2021 based on systematic catches with ordinary mouse traps in traplines. 8 records from Inventaires complémentaires des espèces déterminantes ZNIEFF - Données naturalistes sur des périmètres pour créations de nouvelles ZNIEFF ou atualisation de ZNIEFF existantes. 225 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 1 records from Brenz (Heidenheim). 421 records from Registros Primates Neotropicales Convocatoria APC. 126 records from Mica - Muskrat, Raccoon and Coypu occurrences collected by ITAW in Germany. 19 records from Occurrence of mammalia relicts at site Pestera Livadita. 1967 records from Records of Invasive Non Native Species held on the Cofnod database. 973 records from Spectacled bear database for Peru. 3 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Zicrona - Parcs nationaux. 12 records from Suivi de l'évolution des populations - Regroupement de données opportunistes. 1475 records from Happywhale - Gray Whale in North Pacific Ocean. 2 records from Occurrence of mammalia relicts at site Victoria Cave. 8 records from Bahamas Marine Mammal Research Organisation Aerial Survey. 35 records from Mammals (UWEP-MM). 1 records from Teaching Collection. 1 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Maxime COSSON. 46013 records from Mammals Specimens. 1 records from Artenvielfalt in der Kinderakademie im RFZ. 21 records from Participation aux politiques publiques départementales de l'environnement - Données CEN M-P départements. 64 records from AMAPPS Southeast Aerial Cruise Winter 2013. 136 records from Formación de las colecciones de referencia de aves y mamíferos de la Reserva de la Biosfera de Sian Ka'an, Quintana Roo, México. 259 records from Condon Fossil Collection - Oregon Museum of Natural and Cultural History. 46 records from Empire Wind Digital Aerial Wildlife Surveys for BOEM Lease Area OCS-A 0520, Equinor Wind US LLC, November 2017-October 2018. 209 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Maxime Zucca provenant de la base de donnée du SINP Île-de-France CETTIA. 14 records from Projet de parc éolien en mer des îles d'Yeu et de Noirmoutier - demande de dérogation espèces protégées - Mammifères marins GT - Inventaire non protocolé. 18 records from Occurrence of mammalia relicts at site Erdhöhle. 16 records from Suivis télémétriques de phoques gris par Océanopolis et l'Université de La Rochelle - Observations issues des suivis Argos des phoques gris en Atlantique et Manche Mer du Nord. 3 records from Kenai National Wildlife Refuge, Alaska (KNWR) Mammal observations (Arctos). 1 records from Freiheitsring (Frechen). 1003 records from USAC Mammals Collection. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 24 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Christian Desmier. 46 records from Occurrence of mammalia relicts at site Geißenklösterle. 1 records from Bird Collection of Museum and Institute of Zoology PAS. 666 records from Sizing Ocean Giants. 2341 records from BioGIS - Mammals - SPNI. 5717 records from Données du Parc national des Cévennes - Inventaire et suivis d'espèces dans le Parc national des Cévennes. 3 records from Prophetensee Quickborn. 1 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi de l'impact du pâturage ovin sur la végétation du massif de Fontainebleau. 366 records from Monitoring of the effects of Belgian wind mill parks on benthic macro-invertebrates and the fish fauna of soft substrates - reference situation. (WINMON). 1 records from Plan de gestion 2017 - 2021 du site «Coteaux de Brungidour et des Foncillières» (24) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par Vya Natura (étude de l'avifaune nicheuse). 1 records from CS Trou du Mouton. 21172 records from Weddell Seal Sightings, Vestfold Hills, Antarctica. 2672 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 7531 records from MfN - Fossil vertebrates IV. 4 records from Projet éolien La Grande Lande (53) - Taxons tous groupes inventoriés sur la zone du projet de Grande Lande. 1 records from Eulachon migration bottom trawl surveys. 8 records from Conventions de partenariat sur les terrains militaires d'Occitanie - Données convention de gestion CEN MP - autorités du camp militaire (Camp du Larzac). 25 records from Suivis faunistiques du site du Moulin de la Ville - Données opportunistes. 18 records from Occurrence of mammalia relicts at site Zigeunerfels. 164 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes opportunistes de Sandy Barberis. 1085 records from Gunma Museum of Natural History, Mammal Specimen. 218 records from NMML Harbor Porpoise Vessel, SE Alaska, Fall 1992. 3 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Provost Romain provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Données espèces - Expertise IPE 120. 64 records from Réseau Loup - Lynx ONCFS - Lynx 1994 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 16 records from Ville de Trois-Rivières - Bioblitz 2012. 106294 records from Fauna Atlas N.T.. 5 records from Inventaires naturalistes du Service du Patrimoine naturel / UMS PatriNat - Inventaire de l'îlot du Lédénez Vraz. 93 records from Registros de quirópteros de tres localidades del caribe colombiano. 4340 records from EDP Foz-Tua: Large Mammals (diurnal transects): Ecological Monitoring Program [2011-2017]. 139 records from Réseau Loup - Lynx ONCFS - Lynx 2009 présence Occasionnelle Mailles_10km_LAEA Réseau Loup-Lynx ONCFS. 1 records from Plan régional d'actions en faveur des odonates (PRAO) : 3ème phase (2017 - 2018) menée par le CEN Aquitaine - Observations faunistiques fortuites réalisées lors de journées de prospections animées par le CEN Aquitaine. 4 records from Inventaire des mammifères (hors chiroptères) pour le parc solaire de Ribeyret. 45 records from Regroupement d'études et inventaires - Données opportunistes. 9 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 3265 records from Hedgehogs of Ireland. 74 records from SILENE-FAUNE-PACA - Yoann_BLANCHON_2017_12_18. 9 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Marc CORAIL. 11 records from Elaboration du DOCOB du site Natura 2000 ’Réseau hydrographique du Midou et du Ludon’ (FR7200806) - Inventaire et regroupement de données Natura 2000. 7337 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 13 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 1997. 1 records from Atlas de la Biodiversité Communales sur la Communauté de Commune de Montesquieu - Observations d'odonates et de lépidoptères (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 11 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Mammifères - Inventaire non standardisé - FRAPNA74 - 24HNAT. 7 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi naturaliste du Parc du Peuple de l'Herbe. 1 records from Occurrence of mammalia relicts at site Egtved. 3 records from MSB Mammal Observations (Arctos). 14 records from HRC CRC Small Vessel-Based Monitoring Surveys October 2009. 5 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 40 records from Species biodiversity transnational geo-database - IMPRECO Project. 824 records from Mammalia fossil Kleinsäuger - SMF. 75 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur Le Cesne Maxime. 1 records from History of Life Exhibition. 44 records from Occurrence of mammalia relicts at site Burghöhle Dietfurt. 6 records from SIO Marine Bird and Mammal Survey 2004. 43 records from UNCW Hatteras Aerial Survey - Left side - 2016. 292 records from Northern elephant seals post-breeding 2018 (aggregated per 1-degree cell). 14181 records from Données de Mammifères issues de Baznat. Midi-Pyrénées - Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 429 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Cédric JACQUIER. 6 records from NEFSC 1995 pe9502. 71 records from Biodiversidad asociada al proyecto Línea de Transmisión de Energía Segundo Circuito San Lorenzo - Calizas a 110 kV, Antioquia. 2249 records from Registros de vertebrados durante el fototrampeo de uso de hábitat de yaguarundí en caña de azucar, convenio 105-2017 entre Panthera y CVC. 204 records from Database of Australasian Vertebrate Occurrences. 2 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 62 records from Actions Natura 2000 - Données CEN L-R N 2000. 1020 records from Collection Paleoanthropology SMF. 61 records from Inventaires menés dans le cadre du Groupe Invertébrés de Midi-Pyrénées (GIMP) - Données invertébrés en Midi-Pyrénées. 20 records from Caracterización Ecológica de los Mamíferos del Cerro Jánano. 44 records from ONCFS Réseau Ours brun - Ours 2010 présence Régulière Mailles 10km LAEA Réseau Ours brun ONCFS. 10 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Loïc SALAUN. 31 records from Virginia CZM Wind Energy Area Survey- Left side - January 2014 through March 2016. 65 records from Cetacean observations in the waters of Karaginsky Island and Beringa Island in 2009. 24 records from East Ayrshire Species Database. 4 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Comité_Foin_de_Crau_2017_12_18. 399 records from Otter (Lutra lutra), Outer Hebrides. 26 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 4 records from HRC USWEX Vessel-Based Monitoring Surveys May-June 2008. 6090 records from Irish Whale and Dolphin Group. 2 records from Données espèces - Expertise IQE 308. 4 records from Données espèces - Expertise IQE 95. 34 records from The Taiwan Breeding Bird Survey Data. 14220 records from Observations.be - Non-native species occurrences in Wallonia, Belgium. 2 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 3 records from Elgin Road 3 year observations. 1 records from Plan de gestion 2018 - 2022 du site des Coteaux de Pujols (33) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 61 records from Aerial Survey Baseline Monitoring in the Continental Shelf Region of the VACAPES OPAREA: January 2016 - December 2016 (right side). 58 records from CalCOFI marine mammal surveys 2004-2008 - off effort. 171217 records from Programa de fotomonitoreo de objetos de conservación y amenazas en el Sistema Nacional de Áreas Silvestres Protegidas del Estado (SNASPE). 8 records from SILENE-FAUNE-PACA - BARTH-Environnement_2017_12_18. 91 records from Happywhale - Minke Whale in Southern Ocean. 2118 records from INNS Data: All Taxa (South East Wales). 25119 records from Naturalis Biodiversity Center (NL) - Mammalia. 41 records from Phenological Center - Mammals (Murmansk). 4 records from Occurrence of mammalia relicts at site Steinheim an der Murr. 31 records from UNCW Hatteras Aerial Survey -Left side- 2017. 166 records from Зимние маршрутные учеты в заповеднике «Малая Сосьва» (Ханты-Мансийский Автономный Округ). 132 records from AMAPPS Southeast Aerial Cruise Spring 2017. 224 records from Inventario de los murciélagos de los parques nacionales Sierra de San Pedro Mártir y Constitución de 1857, Baja California, México. 9 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 1996. 10 records from Construction du village Alzheimer à Dax (40) - Inventaire de la Faune patrimoniale. 1 records from Gelände des IVL (Zeckern). 52 records from MVZ Mammal Observations (Arctos). 22 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 8 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Anaelle WILLER. 1 records from Implantation d'une centrale photovoltaïque au sol à Chacé - Etude écologique. 70 records from Réseau Loup - Lynx ONCFS - Lynx 2002 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 95 records from Inventario de Mamíferos Mámbita. 45794 records from Canadian Museum of Nature Mammal Collection. 1430 records from Bases para el monitoreo de dos especies de carnívoros medianos en la Reserva de la Biosfera de Mapimí, Durango. 38 records from ONCFS Réseau Ours brun - Ours 2007 présence Régulière Mailles_10km_LAEA Réseau Ours brun ONCFS. 2 records from Seodaemun Museum of Natural History Mammal. 59978 records from Estonian Nature Observations Database. 14058 records from NCSM Mammalogy Collection. 1 records from 76 - Bois de Beaumont - Chiroptères. 336 records from Campagnes REMMOA (REcensement des Mammifères marins et autre Mégafaune pélagique par Observation Aérienne) - Données d'occurrence de mammifères marins des campagnes REMMOA - Observatoire PELAGIS UMS 3462 et Agence des aires marines protégées. 1 records from Fish assemblages across artificial and natural reefs in Puerto Rico. 1 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 23 records from HRC CRC Small Vessel-Based Monitoring Surveys November-December 2006. 10 records from Sudeniederung (Amt Neuhaus). 1 records from DFO Pacific Groundfish Synoptic Trawl Surveys - Hecate Strait. 30317 records from Royal Belgian Institute of Natural Sciences Mammal collection. 2 records from Hamberger Brücke / Würmtal (Pforzheim). 9 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Syndicat_Mixte_d'Aménagement_de_la_Vallée_de_la_Durance_2017_12_18. 24 records from Registros de mamíferos de los Parques Ecológicos Distritales de Montaña de Bogotá, D.C.. 2633 records from Fife Nature Records Centre combined dataset. 2 records from Hemmerder Schelk (Unna). 30998 records from Elephant Seal Sightings, Macquarie Island. 2 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Pierre SELIQUER. 1 records from Inventaires de la RN d'Arjuzanx - Données opportunistes récoltées lors de missions de terrain des agents. 4 records from Parc éolien de la Société d’Exploitation du Parc Eolien des Noues à Blacy (51) - Points d'écoute au sol des chiroptères. 26 records from Plan de gestion 2009 - 2013 du site des Grottes de Sare (64) mené par le CEN Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 32 records from Mammal specimens of Kawasaki Municipal Science Museum. 30 records from Weanling Northern Elephant Seals (aggregated per 1-degree cell). 448 records from Diagnóstico del aprovechamiento de flora y fauna por los mayas del Ejido Petcacab y evaluación de la cacería y pesca, Felipe Carrillo Puerto, Quintana Roo. 153 records from Protocole de recensement des collisions entre la faune sauvage et les véhicules du département des Pyrénées-Atlantiques - Données de mortalité de la faune par collision avec les véhicules sur le réseau routier du département des Pyrénées-Atlantiques - 2019- 2020. 6 records from RD752 – CRENEAU A 2 X 2 VOIES ENTRE SAINT-PIERRE-MONTLIMART ET BEAUPREAU / COMMUNES DE MONTREVAULT-SUR-EVRE ET BEAUPREAU-EN-MAUGES - RD752 CD49 SAGE Juillet 2014 - aout 2015. 27 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Philippe GOURDAIN (ANVL). 5 records from Rare species of animals and plants of the flood zone of the Oleksandrivka Reservoir of the Buzk's Gard National Nature Park. 66 records from AMAPPS Southeast Aerial Cruise Spring 2014. 517 records from Distribution ashore of Southern elephant seals in Península Valdés. 3 records from Happywhale - Polar Bear in North Pacific Ocean. 13 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 437 records from Données Faune Base SIRFF - FNE Centre-Val de Loire - Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2015. 95 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 13 records from Occurrence of mammalia relicts at site Kartstein. 176 records from Marine Mammal Observation - Total Denmark 2013-2020. 27 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Vincent Vignon. 6 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 6 records from Parc éolien de La Bussière - Données biodiversité. 63 records from Inventaires chiroptérologiques pour l'amélioration de la connaissance de la biodiversité et des habitats des chauves-souris - Données invertébrés GCMP. 165 records from SWFSC Marine Mammal Survey, MOPS 1989, Cruise 1267. 496 records from CLICNAT- Base de données naturaliste picarde - Données de terrain du CPIE des Pays de l'Aisne. 5 records from SILENE-FAUNE-PACA - CG04_2017_12_18. 1 records from Occurrence of mammalia relicts at site Seest. 6 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 15880 records from CUMV Mammal Collection. 23 records from Genética de la Conservación del Oso Andino en las áreas protegidas de Paramillo, Palermo, Santurbán, Yariguíes y Serranía del Perijá. 1 records from Schulgelände Lise Meitner Realschule (Paderborn). 2 records from Kurler Busch (Scharnhorst). 6 records from Occurrence of mammalia relicts at site Buchenloch. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 9454 records from SMRU Grey Seal UK 1991-1993. 329 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Xavier JAPIOT. 3 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Nathan HAUQUIN. 373 records from Otter survey of Ireland 2004 & 2005. 6 records from Occurrence of mammalia relicts at site Tokod-Nagyberek. 1 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Grosso Eric provenant de la base de donnée du SINP Île-de-France CETTIA. 42 records from ONCFS Réseau Ours brun - Ours 2011 présence Régulière Mailles 10km LAEA Réseau Ours brun ONCFS. 1063 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Wolf, (Canis lupus) Wild Boar (Sus scrofa) and Roe Deer (Capreolus capreolus) [camera-trapping] - [2011-2014]. 7 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 10 records from Faberpark (Nürnberg/Stein). 13723 records from Harbour seals GPS telemetry in Baie du Mont Saint-Michel. 7 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 529 records from Vertebrates (except birds, INNS and restricted records), Outer Hebrides. 4 records from A survey of small mammals in the Volta Region of Ghana with comments on zoogeography and conservation. 5 records from Occurrence of mammalia relicts at site Pestera lui Climente I. 205 records from Some finds of birds, mammals, amphibians and reptiles in autumn and winter 2021 - 2022 in Kharkiv region, Ukraine. 236 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 106 records from Evaluación y monitoreo de manglar en la Reserva de la Biósfera Los Petenes con énfasis en criterios de sustentabilidad y desarrollo. 1 records from Tornoer Teich. 15 records from UNCW JAX Aerial Survey -Left side- 2017. 2 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de D'ONOFRIO Patrice. 1 records from Happywhale - Pygmy blue whale in Indian Ocean. 209 records from MVZ Hildebrand Collection (Arctos). 195 records from SEFSC Southeast Cetacean Aerial Survey 1992. 7764 records from SILENE-FAUNE-PACA - Parc_National_du_Mercantour_2017_12_18. 7640 records from CEDaR Online Recording. 5 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaire Faune Flore du Cirque de l'Essonne. 1527 records from National Biodiversity Data Bank. Observation records, 1900-2014. 2 records from Etude préalable au plan de gestion des lagunes d'Hourtin pour la protection des sites à leucorrhines menée entre 2015 et 2019 par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 1 records from Happywhale - Harbor Seal in Southern Ocean. 41 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 59 records from ONCFS Réseau Ours brun - Ours 2012 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 25 records from Ecología y manejo de ungulados cinegéticos en el sur de Baja California Sur. 756 records from NWTRC JP02 Marine Mammal Aerial Surveys in the Puget Sound 2013. 13 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Delphine MONTAGNE. 7 records from Enquête sur 3 mammifères protégés : le Muscardin, le Campagnol amphibie et la Crossope aquatique - Données mammifères Phase 1 récoltées par Charente Nature. 1 records from 59 - Beau Gui Chiroptères. 180 records from New Mexico Museum of Natural History and Science (NMMNHS) Paleontology specimens (Arctos). 8805 records from California State University, Long Beach Mammals. 32914 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 981 records from Monitoreo de la ocupación del Oso Andino (Tremarctos ornatus) en el Parque Nacional Natural Chingaza. 3357 records from Données de Mammifères issues de Baznat. Midi-Pyrénées - Données mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 2. 1 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 1 records from Nottekanal, Klasse 7 - 10. 3 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 121 records from Clare Biological Records Centre Dataset 2004-2007. 36 records from Caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 83 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Vouharte. 3009 records from National Trust for Scotland Species Records. 212 records from NEFSC North Atlantic Marine Mammal and Turtle Aerial Abundance Survey 2007. 2 records from Wanderweg am Windebyer Noor (bei Eckernförde). 7 records from Happywhale - Southern Elephant Seal in Southern Ocean. 2 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Etude d'impact quartier du Bréau à Fontainebleau. 170 records from Fauna marina de la costa vasca - Sistema de Información de la Naturaleza de Euskadi. 2 records from Base BOMBINA du Parc Naturel régional Lorraine - Données diverses Parc naturel régional de Lorraine. 14 records from HRC CETOS Vessel-Based Monitoring Surveys January 2007. 2151 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 3958 records from Gray whale visual sightings from shore 2014-2015. 9 records from Inventaire dans le cadre des missions Natura 2000 - Données Faune. 30 records from Grand Rhinolophe et trame verte bocagère en Poitou-Charentes - Données sur les colonies de reproduction et d'hivernages des chiroptères de Charente-Maritime. 1 records from Happywhale - Minke Whale in South Pacific Ocean. 5 records from données sur les ENS - données opportunistes sur les ENS 17 par l'association Environat. 49 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Atlas de la Biodiversité de Seine-et-Marne - volet 2. 382 records from EDP Foz Tua - Terrestrial Vertebrates (occasional observations) - Ecological Monitoring Program [2011-17]. 59 records from Fauna y flora del municipio de Lipa, Arauca. 12 records from Annotated checklist of bats (Mammalia: Chiroptera) of Mount Cameroon, southwestern Cameroon. 192 records from Loup 2009 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 14674 records from Données du Réseau d'observateurs des mammifères marins en mer de la Manche - Observations du Grand dauphin du Golfe normand-breton. 96 records from Estado actual del conocimiento biológico de algunas especies de roedores de las familias Muridae, Geomyidae, Heteromyidae y Sciuridae (Rodentia: Mammalia) incluidas en el PROY-NOM-059-ECOL-2000. 117 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 79 records from Occurrence of mammalia relicts at site Velika Pecina. 1 records from Biodiversity Surveys, South-east Arnhem Land. 3 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Fourrier Thibault provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Centrale photovoltaïque de Lux - Données faune/flore CAEI. 4741 records from Making the zoology collection at the Natural History Museum of Zimbabwe accessible through GBIF by end of 2017 (BID-AF2015-0117-SMA). 18 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 43 records from DASSH Data Archive Centre volunteer sightings records. 147 records from Tartu University fossil collections. 8 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" de Sabaille (CRÉON D'ARMAGNAC). 28 records from Happywhale - Blue Whale in Southern Ocean. 11104 records from Happywhale - Humpback Whale in North Atlantic Ocean. 936 records from EDP Foz-Tua: Large and Medium-sized Mammals (point counts): Complementary Studies [2009-10]. 1 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi du Sonneur à ventre jaune en vallée du Petit Morin. 60494 records from TTU Mammals Collection. 1 records from Population research on small rodents (Rodentia) and shrews (Soricidae) in Lierne Municipality – Norway; 2018-2021 based on systematic catches with ordinary mouse traps in traplines. 8 records from HRC CRC Small Vessel-Based Monitoring Surveys May 2011. 2 records from Reconnaissance survey in Block 12 - TotalEnergies Oman. 19 records from Biodiversidad asociada al proyecto Parque Solar Fotovoltaico Tepuy. 5 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Champagne Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 1357 records from Large herbivores in African savannahs, Lake Mburo National Park, Uganda. 15 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 419 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 1 records from Données espèces - Expertise IPE 28. 8 records from Occurrence of mammalia relicts at site Geyerloch. 3 records from Mammalia (JNHM-MM). 3 records from Classic localities of endemic amphibians, reptiles and mammals from the Western Balkans. 13 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Rapport de mission Saint-Pierre et Miquelon. 2 records from Plan de gestion du Site des Sources - Inventaire Faune. 542 records from Shire Group IDB species data 2004 to present. 3 records from PROJET DE CENTRALE PHOTOVOLTAÏQUE A MAUGES SUR LOIRE - données faune flore, centrale photovoltaïque de Mauges sur Loire (49). 71 records from AMAPPS Southeast Shipboard Cruise Summer 2016. 2 records from Renouvellement de l'autorisation d'exploiter une carrière à Hoerdt - Etude écologique - Inventaires faune-flore 2016. 10 records from Mamíferos Asociados al Cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO. 1103 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Seine-et-Marne Environnement provenant de la base de donnée du SINP Île-de-France CETTIA. 24 records from Projet Patrimoine Naturel - Club Biodiversité - Club Biodiversité tous groupes taxonomiques. 2 records from WildesMoor bei Schwabstedt. 155 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du Parc Naturel Régional de la Haute Vallée de Chevreuse provenant de la base de donnée du SINP Île-de-France CETTIA. 234 records from Loup 2012 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 2 records from PARC PHOTOVOLTAIQUE à RIANS - Faune. 217 records from SWFSC Marine Mammal Survey, STAR 2003, Cruise 1623. 24 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données de ABGRALL Jean-François, Département Santé des Forêts, Ministère de l'agriculture. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données malacologiques de Joël Bec. 66 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 6 records from Suivi de passerelles flottantes - Données de pièges-photos sur 2 passerelles flottantes en marais de Rochefort en Charente-Maritime. 31 records from Albury Wodonga Nature Map. 365 records from Registros del inventario y monitoreo de la Biodiversidad en la Jurisdicción de la Corporación Autónoma Regional de Cundinamarca CAR. 34 records from AFAST Hatteras Aerial Survey -Left side- 2011-2012. 2 records from Weinberg Reichersdorf. 14 records from Happywhale - Bowhead in Arctic Ocean. 33 records from Waterbird counts, Luomus dataset. 2 records from Plan de gestion 2014 - 2018 de la Réserve Naturelle Régionale des carrières de Tercis-les-Bains (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 165 records from Happywhale - Minke Whale in North Pacific Ocean. 5 records from Occurrence of mammalia relicts at site Kogelstein. 14915 records from Mammal specimens. 4 records from ferme solaire de Marcoussis - données fauneflore. 9149 records from ISM Mammalogy Collection. 223 records from Coleção de Mamíferos da Universidade Estadual do Norte Fluminense. 4430 records from Enquêtes sur les écureuils de France - Enquête nationale sur les écureuils de France. 238 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocapra americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 22 records from Colección del Museo de Ciencias Naturales “José Lorca”. 2 records from Inventaires sur le réseau Aquitaine Nature du PNR Périgord-Limousin - Inventaire dans la Vallée du Repaire. 1 records from Valentin Moser Bats. 30 records from Animal observations. 31 records from Base BOMBINA du Parc Naturel régional Lorraine - Données diverses du Parc naturel régional de Lorraine. 9 records from Occurrence of mammalia relicts at site Fuchsloch im Krockstein. 64 records from Consolidación y sistematización de las colecciones de referencia de peces y mamíferos marinos del ITESM Campus Guaymas. 4 records from SILENE-FAUNE-PACA - SYMBIOSE_2017_12_18. 25995 records from Atlas of Mammals in Ireland 2010-2015. 22 records from Bioimages. 16 records from Occurrence of mammalia relicts at site Vindija. 446 records from Réserves Naturelles de France (RNF) - Données RNF - PNR des ballons des Vosges. 1 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaire faune et flore sur l'ancien bassin du Breuil à Sainte-Geneviève-des-Bois -91. 304 records from Fort Hays State University Sternberg Museum of Natural History - Vertebrate. 1675 records from Land-based observations of cetaceans in the waters of Beringa Island in 2007-2009. 22913 records from Museums Victoria provider for OZCAM. 1 records from Occurrence of mammalia relicts at site Ejstrup. 2332 records from Plan de vertebrados de la Patagonia. 2 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Quentin MOLINA. 28 records from DUML vessel-based surveys for proposed JAX USWTR site 2009-2011. 14 records from NMML Harbor Porpoise Aerial Survey, Alaska Peninsula, Replicate 2, 1992. 1892 records from SysTax - Zoological Collections. 1 records from Appui technique et scientifique aux réserves naturelles (nationales et régionales) - Données invertébrés RNN CEN L-R. 30 records from Données opportunistes du Parc Naturel Régional Périgord-Limousin (PNRPL) - Données faune avant 2006 de la BDAccess du PNRPL. 1 records from Occurrence of mammalia relicts at site Igstadt I. 1554 records from Activité générale du bureau d'étude BIOTOPE (1994 - 2013) - Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 132 records from SILENE-FAUNE-PACA - LPO_PACA_2017_12_18. 160 records from MfN - Fossil vertebrates III. 13177 records from Harbour seals GPS telemetry in Baie de Somme. 291 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données naturalistes hors Île-de-France saisies dans Cettia-idf. 5066 records from HSU Vertebrate Museum Mammals Collection. 68 records from UWIZM Mammals. 13907 records from Mammal Records (West Wales). 202 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 819 records from Seabirds of the Southern and South Indian Ocean. 569 records from Observatoire Pelagis boat surveys 2003-2021. 3402 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 2 records from Fauna Species of Camiguin Island, Philippines. 8 records from Sightings for Airborne Mine Neutralization System Aerial Monitoring in the NSWC PCD Study Area from October 2011, 2012. 21 records from Monitoreo de mastofauna en corredores biológicos de Chiapas. 10 records from Occurrence of mammalia relicts at site Bivak Cave. 6 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de DURON Cyril. 189 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 87 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 180 records from Northern Territory WildWatch. 6 records from NMML Harbor Porpoise Aerial Survey, Cook Inlet, 1991. 5 records from Elaboration du DOCOB du site Natura 2000 ‘Marais du Bas Médoc’ (FR7200680) - Inventaire Faune. 28 records from CRC HRC PMRF Small Vessel-Based Monitoring Surveys February 2015. 6 records from Landschaftspflegehof (Berlin). 44 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 1 records from Animation du Document d’objectifs du site Natura 2000 FR7200799 - Carrières de Castelculier (47) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Nouvelle-Aquitaine. 7 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 125 records from WDC Lewis survey data. 12 records from Gemeinde Sursee. 140 records from Elaboration du DOCOB du Parc Naturel Régional des Landes de Gascogne - Inventaire de la faune réalisé par Jérôme Fouert. 852 records from Données de l'Observatoire des Mammifères marins de l'Archipel Guadeloupéen - Observatoire des Mammifères marins de l'Archipel Guadeloupéen. Suivi Dauphins Les Saintes. 6 records from Occurrence of mammalia relicts at site Nazeing. 2 records from Artenvielfalt auf den Elbwiesen (Dessau). 1 records from Seabird and cetacean sightings from Cruise SY002 of RV Shoyo Maru, Tropical Atlantic Ocean, Oct. 2000. 2239 records from TWIC Hedgehog Public Survey. 3 records from UNCW PAX Aerial Survey - Right side - 2016. 6 records from installation d'une centrale au sol d'energie solaire sur l'ancienne ISDND de SUEZ RV à Milhac d'Auberoche - DONNEES BIODIV MILHAC. 4 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 1995. 27 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 35 records from NMML Harbor Porpoise Aerial Survey, Kodiak Island, Replicate 3, 1992. 19 records from Mammals specimens of Taga Town Museum, Shiga Pref., Japan. 6 records from Noosa Shire Nature Map. 3 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 3137 records from Estonian Naturalists’ Society. 34431 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 687 records from Données du programme 50000 observations pour la forêt. 2538 records from Protocole de recensement des collisions entre la faune sauvage et les véhicules de la Direction interdépartementale des routes Centre-Est - Données de mortalité de la faune par collision avec les véhicules sur le réseau routier de la DIR Centre-Est. 42 records from SILENE-FAUNE-PACA - Département_du_Var_2017_12_18. 2 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 172 records from Vertebrados registrados durante el muestreo de tigrillos melánicos en el Valle del Cauca. 1 records from Seabird observations on the RV Falkor, Voyage FK210206, Coral Sea, Australia (2021). 40 records from MIRC NAVFAC Incidental Sightings - Vessel 1965-2014. 9 records from Projet de parc éolien en mer des îles d'Yeu et de Noirmoutier - demande de dérogation espèces protégées - Mammifères marins PT - Inventaire non protocolé. 1 records from Wildlife Observations Bardon Hill 31.5.09. 2 records from ACCDC: Rare Species in Atlantic Canada and Adjacent Marine Waters. 7 records from Inventaire en continu de la ZNIEFF 'Forêt du Verdus' - 720012953 - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 1793 records from Locations of seals in Patagonian Large Marine Ecosystem (OBIS South America, AR-OBIS, Sub-node). 54 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes opportunistes de Sylvain BONIFAIT. 11 records from Occurrence of mammalia relicts at site Zemst Bos van A. 1794 records from Base de données faune - DREAL Centre-Val de Loire. Polygones. 10 records from Woodland Survey. 52 records from Mammal specimens of Okinawa Prefectural Museum & Art Museum. 3 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 298 records from Modelado de la distribución geográfica de mamíferos endémicos y en riesgo de conservación de Oaxaca. 7682 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 14 records from University of Algarve and ICNB Cetacean Sightings 1999. 63 records from Réseau Loup - Lynx ONCFS - Lynx 2009 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 8 records from Happywhale - Leopard seal in South Pacific Ocean. 4 records from MIRC Saipan Marine Species Monitoring Winter-Spring Surveys 2012. 66 records from Plan d'actions du Canal des Deux mers en Midi Pyrénées - Données patrimoine naturel Canal des deux mers et Canal du Midi. 2 records from Plan de gestion 2012 - 2016 du site des tourbières de Mées (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 318 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 581 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 23 records from ÉDUCATION À L'ENVIRONNEMENT - CLUB NATURE - Données tous groupes taxonimiques du Club Nature. 967478 records from iNaturalist Research-grade Observations. 296 records from SEFSC GoMMAPPS 2018 Fall Aerial Survey. 24 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Ouest. 1 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 10237 records from Inventaire des Mammifères de France - Inventaire des Mammifères marins de France (métropole et outre-mer). 3 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Curtelin Laure-Angélique provenant de la base de donnée du SINP Île-de-France CETTIA. 64 records from Réseau Loup - Lynx ONCFS - Lynx 1996 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 44 records from Données du Parc National de la Guadeloupe - Données Racoon sur le territoire de la Guadeloupe. 2 records from Centrale solaire Zac de l'Empereur - Etude d'Impact Données Faune. 433 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2018. 3 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de LAMBERT--GRIMPARD Corentin. 2 records from Hintere Halde. 1 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste DUFRENE ERIC provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Projet de création d'une usine de fabrication de granulés de bois sur la commune d'Anor (59) - Expertise faune flore- TAUW FRANCE - avril 2017. 2357 records from Visual sightings from Song of the Whale 1993-2013. 1 records from Synthèse de la Répartition des populations de cerf élaphe en 1995 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1 records from Stadt Königs Wusterhausen. 516 records from Atlas of Life in the Coastal Wilderness. 6 records from Gunma Museum of Natural History, Vertebrate Fossil Specimen. 8710 records from Occurrence de mammifères du Groupe d’Étude des Mammifères de Lorraine - Compilation des données "Carnivores" en Lorraine. 17 records from Visual contacts from research cruises in the Med sea, 1994-2001. 3 records from Additional records of Cantor’s Leaf-Nosed Bat Hipposideros galeritus Cantor, 1846 (Mammalia: Chiroptera: Hipposideridae) in eastern India: Odisha. 16 records from Genética de la Conservación del Oso Andino en el Parque Nacional Natural Cordillera de los Picachos y área de amortiguación. 4 records from Plan Local d'Urbanisme (PLU) de La Brède - Inventaire faune. 55 records from Happywhale - Blue Whale in North Atlantic Ocean. 47 records from Insectivorous Bats of Gunung Mulu National Park, Malaysia. 47 records from NMML Harbor Porpoise Aerial Survey, Kodiak Island, Replicate 1, 1992. 1 records from Mißmahlsche Anlage. 7 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Biermé Claire provenant de la base de donnée du SINP Île-de-France CETTIA. 53 records from Regroupement d'études et inventaires - Collecte données faune Simethis 2014-2019. 3003 records from Passive acoustic monitoring of killer whales in the northern Gulf of Alaska. 1715 records from Modelado de la distribución potencial de las musarañas (Mammalia, Soricidae). 6 records from Census of plant and animal species in sacred forests of RAMSAR sites 1017 and 1018 in Benin. 11 records from MIRC NAVFAC MISTCS Vessel Surveys Jan-Apr 2007. 1295 records from Mamíferos asociados a un bosque húmedo tropical de Barrancabermeja, Santander. 186 records from SOCAL Marine Mammal Aerial Monitoring 2010. 481 records from Peces y Mamíferos de la región de Norogachi, Alta Sierra Tarahumara, Chihuahua (Mamíferos). 49 records from AFTT Cape Hatteras Aerial Survey -Right side- 2014. 13 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Arnaud Bak. 3004 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 3 records from Biodiversity Survey of Echuya forest, Year 2012. 16 records from Biological Recording in Scotland - Scotsman Wildlife Surveys. 2 records from FERME ÉOLIENNE DE BLANZAY - Chiroptères Blanzay automne 2016. 647 records from Mamíferos de 14 municipios del Departamento del Valle del Cauca para el fortalecimiento de RNSC y Caracterización de Predios Adquiridos para la Conservación de Cuencas. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 3 records from WADFW PSAMP W1996. 4 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM). 1842 records from Ecología y genética poblacional de la ballena gris Eschrichtius robustus en la Península de Baja California. 5 records from Mutualisation des données ZNIEFF en ex-Limousin - Données chiroptères transférées du GMHL à LNE. 12 records from UNCW JAX Aerial Survey -Right side- 2017. 20 records from CRC HRC PMRF Small Vessel-Based Monitoring Surveys February 2016. 16 records from Censo de ardeidas invernantes y nidificantes de la Comunidad Autónoma del País Vasco. 48 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes opportunistes de Cedric DEVILLEGER. 1 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Thomas ARMAND. 425 records from Skull morphology and functionality of extant Felidae (Mammalia: Carnivora): a phylogenetic and evolutionary perspective. 24 records from Caracterización de la fauna y flora presente en los predios propuestos para el plan de restauración del distrito de conservación de suelos del cañon de rio grande (DCS-CRG), en el municipio de Dagua. 48 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 25 records from Análisis de las poblaciones de oso palmero (Myrmecophaga tridactyla) en el Departamento del Meta. 42 records from Coordination PRA Loutre et suivi du castor en Limousin - Inventaire Mammifères Aquatiques. 93 records from Liste d'espèces animales recensées au cours des activités de l'Organisation pour le Développement Durable et la Biodiversité (ODDB ONG) au Bénin. 1 records from Projet 3B Biodiversité Biomasse Bordeaux - Inventaire et suivi Faune. 12436 records from University of California Museum of Paleontology. 8 records from NMML Harbor Porpoise Aerial Survey, Alaska Peninsula, Replicate 1, 1992. 47 records from Happywhale - Fin Whale in South Atlantic Ocean. 1 records from Acoustic detections from research cruises in the Med sea, 1994-2001. 3207 records from Observatoire Pelagis aerial surveys 2002-2021. 1146 records from Données opportunistes capitalisées par la DREAL Corse (OGREVA) - Dreal Corse - Base Ogreva. 2 records from Mesures agro-environnementales et climatiques (MAEC) - Données MAEC CEN LR. 1822 records from Data on animal species in the Biosphere Reserve of W Bénin. Data mobilized in the framework of JRS Biodiversity Foundation funded project in Benin. 1921 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 117 records from Tethys Research Institute aerial survey cetacean sightings 2009-2011. 3 records from Assistance technique menée par le CEN Aquitaine pour la gestion et les suivis scientifiques des ENS du Département de la Dordogne (24) - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Nouvelle-Aquitaine. 1029 records from Dorset SW Pilot species dataset. 8 records from Etude naturaliste du projet de parc éolien de Londigny Energies. 16 records from Mesures compensatoires autoroutes - Données mesures compensatoires ASF - ex région M-P. 51 records from (Table A1) Annual biomass of plants and animals recorded on Bylot Island between 1993-2009. 3 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste zeitouni kevin provenant de la base de donnée du SINP Île-de-France CETTIA. 67 records from Réseau Loup - Lynx ONCFS - Lynx 2010 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 190 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 2012. 73 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Philofauna provenant de la base de donnée du SINP Île-de-France CETTIA. 16041 records from NEFSC Right Whale Aerial Survey. 29260 records from Villreinobservasjoner. 1 records from Synthèse de la Répartition des populations de cerf élaphe en 1985 (réseau Ongulés sauvages ONCFS-FNC-FDC). 41 records from Registros de mamíferos de los Parques Ecológicos Distritales de Humedales de Bogotá, D.C.. 9573 records from Cumbria Non Native Invasive Species. 31 records from Gulf of Maine humpback whale satellite tagging project: 2015 (aggregated per 1-degree cell). 140 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 184 records from HRC SCC Aerial Shoreline Surveys February 2012. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Pierre-Alexis RAULT. 1 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Nicolas SECONDAT. 2355 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 2442 records from data.mnhn.lu observation data. 45 records from Réseau Loup - Lynx ONCFS - Lynx 2000 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 14 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Esnault Sarah provenant de la base de donnée du SINP Île-de-France CETTIA. 25 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Philippe LEGAY. 4 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Sébastien Siblet. 27629 records from African Mammalia. 1672 records from Happywhale - Humpback Whale in Indian Ocean. 10 records from Occurrence of mammalia relicts at site Bettelküche. 10 records from Projet éolien de Liniez II - Inventaires écologiques. 485 records from Inventario faunístico de dos regiones terrestres prioritarias de la península de Baja California: San Telmo-San Quintín y Planicies de Magdalena (Ejemplares). 1 records from Ahuyentamiento, rescate y reubicación de fauna en el área de influencia directa del proyecto Hidroeléctrico Mulatos II. 10 records from Lizard Island Research Station. 10 records from Programmes d'Atlas de la biodiversité communale (ABC) - Atlas de la Biodiversité Communale sur les communes de Montmaurin, Lespugue et Blajan - Haute-Garonne - Données du CEN MP. 242 records from IIAPPoa. 588 records from Distribution ashore and breeding places of southern elephant seals. 3 records from Artenvielfalt der Nordsee - Sylt. 35 records from NMML Killer Whale Vessel, Alaska Peninsula 1993. 156 records from Monitoreo de la Fauna Silvestre con Capacitación y Certificación de Monitores Comunitarios en las Microrregiones Prioritarias para la Conectividad y Conservación de la Biodiversidad Agua Blanca, Cañón del Usumacinta, Sierra de Tabasco, *. 2 records from Unser Schulgelände. 5403 records from Suivis télémétriques des pinnipèdes dans les TAAF du Centre d'Etudes Biologiques de Chizé - Suivis télémétriques des éléphants de mer dans les TAAF par le Centre d'Etudes Biologiques de Chizé. 23 records from Primer monitoreo y seguimiento de fauna terrestre para el AID y AII de la Pequeña Central Hidráulica Riofrío. 2018. 5 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Mikaël PAILLET. 28 records from Derbyshire Invasive Non-Native Species (INNS) 1900 - 2014. 21 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Hasrouni Sami provenant de la base de donnée du SINP Île-de-France CETTIA. 1607 records from Programme CarNET B (Cartographie Nationale des Enjeux Territorialisés de Biodiversité Remarquable) - Carnet B Centre - lot 2012. 424 records from UNCW Right Whale Aerial Surveys 2008. 1 records from Plan de gestion 2019 - 2023 de la Réserve Naturelle Régionale des carrières de Tercis-les-Bains (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 30 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Pie verte bio provenant de la base de donnée du SINP Île-de-France CETTIA. 121 records from Réseau Loup - Lynx ONCFS - Lynx 2001 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 77 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 126 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (MZFC_FCMM). 22 records from Occurrence of mammalia relicts at site l´Abri de Rhodes II. 1 records from Occurrence of mammalia relicts at site Mitoc Malul Galben. 7 records from Données espèces Expertise IQE 311. 831 records from MMS Surveys, SCB 1995-1997. 39 records from Monitoreo y seguimiento de fauna terrestre para el AID y AII de la Central Hidráulica de Calima. 2018. 1 records from SILENE-FAUNE-PACA - BIOMEO_2017_12_18. 856 records from India Biodiversity Portal publication grade dataset. 1 records from Inventaires sur le réseau Aquitaine Nature du PNR Périgord-Limousin - Inventaire sur le site de la Pierre levée. 33 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Pierre Rivallin provenant de la base de donnée du SINP Île-de-France CETTIA. 12 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste FAUCHER Alexandre provenant de la base de donnée du SINP Île-de-France CETTIA. 447 records from GOALS Vessel Surveys June - July 2013. 148 records from Lochaber wild boar/feral pig camera trap survey, 2015. 142 records from Plan de gestion 2012 - 2016 de la Réserve Naturelle Régionale d'Errota Handia (64) mené par le CEN Aquitaine - Observations faunistiques (suivi par piège photographique) réalisées par le CEN Aquitaine. 4 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 251 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 12 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Thibedore Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 210 records from CLICNAT- Base de données naturaliste picarde - Données bibliographiques. 859 records from Bosque Mesófilo de Montaña de México. 3062 records from NMNH Paleobiology Specimen Records (USNM). 2 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 1 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 656 records from Stoats in Orkney: records & sightings reported to SNH, 2010 - 2015. 132 records from Collecte permanente de données naturalistes sur la base de donnée participative en ligne de Charente Nature (Faune Charente) - Synthèse 10x10km de la faune sauvage de la Directive Habitats-Faune-Flore recensée par l'association Charente Nature. 18 records from Empire Wind Digital Aerial Wildlife Surveys for BOEM Lease Area OCS-A 0520, Equinor Wind US LLC, February - December 2019. 347 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1437 records from SILENE-FAUNE-PACA - Parc_National_de_Port_Cros_2017_12_18. 28 records from Mammal specimens of Komatsu City Museum. 3 records from observe_tuna_bycatch_ecoscope. 38 records from Natural England bat roost visit records from 2013 onwards. 1 records from Pflanzen und Tiere im Burgwald. 8 records from UNCW PAX Aerial Survey - Left side - 2016. 1 records from Örtzemündung (Stedden). 5 records from 人禾環境倫理發展基金會_2017-2019東北部獨流溪魚蝦蟹螺調查. 3 records from Naturalis Biodiversity Center (NL) - Aves. 1190 records from Tracking data from a free-roaming female cheetah released into the Pilanesberg National Park, South Africa. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Françoise SERRE-COLLET. 264 records from Données Mammifères de l'Association pour les terroirs, les hommes et la nature (Athena) - Occurrence de Mammifères l'Association ATHENA (41) du Perche en Région Centre. 11 records from Occurrence of mammalia relicts at site Sütto_6. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 7245 records from SMRU Elephant Seal Pup Tracking 1995-1996. 4 records from SILENE-FAUNE-PACA - ALP-PAGES_2017_12_18. 4 records from Biologische Station im Kreis Wesel. 1219 records from Actualización de la base de datos de la Colección Regional Durango (Tejido). 14 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Mallard stephane provenant de la base de donnée du SINP Île-de-France CETTIA. 11 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Damien AVRIL. 51 records from USWTR Onslow Bay Aerial Survey -Right side- 2008-2010. 41 records from Réseau Loup - Lynx ONCFS - Lynx 1995 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 24 records from Happywhale - Short-finned Pilot Whale in North Atlantic Ocean. 197 records from EDP Foz Tua Otter (Lutra lutra) [transects] - Ecological Monitoring Program (2011-17). 283 records from Données Association Évasion tropicale (AET) - Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 212 records from Análisis de los efectos ecológicos del aprovechamiento forestal en el Corredor Biológico Mesoamericano: mamíferos, plantas y sus interacciones. 4 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Severine GUYOT. 249 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 2014. 10 records from Ferme éolienne du Briou - Données biodiversité Haimps-Massac. 1727 records from Mammal specimens of Tochigi Prefectural Museum. 235 records from Données de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS 2015 Chiroptères, Maculinea, Cistude d'Europe. 1 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Denis VINCENT. 22 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Julien ROUSSEAU. 780 records from RISC Non-Native Species Records for Muntjac. 8 records from Occurrence of mammalia relicts at site Stematia. 1 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from HRC CRC Small Vessel-Based Monitoring Surveys December 2010. 1 records from Base BOMBINA du Parc Naturel régional Lorraine - Natura 2000 Complexe de l'étang de Lindre, forêt de Romersberg et zones voisines. 2 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 2300 records from Mammal collection NTNU University Museum. 7 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 6 records from PROJET DE PARC EOLIEN DE L’HERBUE - Données Faune Flore du parc éolien de l'Herbue. 2242 records from BioFokus. 609 records from Anymals+plants - Citizen Science Data. 64 records from Regroupement d'études et inventaires - Inventaire et suivi de la faune écrasée. 137 records from nsmk_mm_2019. 1 records from Données espèces - Expertise IPE 6. 13 records from Données CEN L-R LIFE + Envoll. 1612 records from Opportunistic marine mammal sightings from commercial whale watching vessels, Montauk, New York 1981-1994. 1 records from Mollusc collection Natuurmuseum Brabant, Tilburg. 1 records from Flusswerder in der Weser (Hameln). 198 records from Biodiversidad asociada al gasoducto Loop San Mateo-Mamonal. 724 records from Happywhale - Fin Whale in North Pacific Ocean. 2 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Plan d'aménagement Forêt de Claye-Souilly. 2 records from Programmes d'étude et de conservation de populations d'espèces particulières (hors PNA et PRA) - Données CEN M-P espèces. 61 records from Population status, Distribution and Threats to the Nile lechwe (Kobus megaceros, M.T.Von Heuglin,1853) in the Sudd Wetland, South Sudan (2012). 9 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Claire BETBEDER. 30 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 6 records from Occurrence of mammalia relicts at site Bettenroder Berg IX. 50034 records from Fin whale localized acoustic detections off Kauai 2011-2017. 20 records from Occurrence of mammalia relicts at site Roter Berg bei Saalfeld. 109 records from Pedestrian mammals census in W National Park. 387 records from INSDC Host Organism Sequences. 653 records from Océanopolis mammifères marins en Bretagne 1993-2015. 3 records from Auckland Museum NZ Marine Collection. 51 records from Animation technique des sites Natura 2000 ‘Barthes de l'Adour’ - Animation des Docobs des barthes de l'Adour. 1 records from Rotes Steigle (Panzerübungplatz Böblingen). 7 records from Données espèces - Thèse Yvelines 2018-2019. 1 records from Gronau - auf der Suche nach dem Neunauge. 1 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 26 records from Atlas de la biodiversité communale du PNR Golfe du Morbihan - Atlas de la biodiversité communale - Inventaire de la faune d'Elven. 4979 records from Levantamento de Mamíferos do Parque Nacional da Quiçama - INBAC/RWCP - 2017. 5 records from Base BOMBINA du Parc Naturel régional Lorraine - Natura 2000 Etang de Lachaussée et zones voisines. 2 records from Inventaire entomologique standardisé des ZNIEFF de Martinique - Observations diverses réalisées à l'occasion de l'inventaire entomologique des ZNIEFF de Martinique. 1 records from Etat initial de la faune pour la construction de la liaison RD656/RD119 et des carrefours associés (Amorce de la rocade Ouest d'Agen) - Données bibliographiques Faune. 3 records from Entdeckertour am Muldestausee 1/05. 18 records from Plans régionaux d'Action (PRA) - PRA Chiroptères. 6 records from Occurrence of mammalia relicts at site Stellmoor. 24 records from Modification des conditions d'exploitation d'une Installation de Stockage - Etude Faune et Flore 2B Recyclage - L'Hôtellerie de Flée. 106 records from Mammalian Specimens of the Yamagata Prefectural Museum. 127 records from Réseau Loup - Lynx ONCFS - Lynx 2006 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 1244 records from Ghent University - Zoology Museum - Vertebrate collection. 81 records from Fauna y flora de la cuenca media del río Lebrija en Rionegro, Santander. 433 records from Envoi de données complémentaires disponibles à la SFEPM pour l'atlas des Mammifères de France - Données Loutre compilées par la SFEPM pour compléter les cartes de l'atlas national des Mammifères.. 61 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Conseil_Général_83_2017_12_18. 1 records from Parc éolien d'Argillières - chiroptères en altitude. 1 records from Animation du Document d’objectifs du site Natura 2000 FR7200666 - Vallées des Beunes (24) menée par le CEN Aquitaine - Observations faunistiques (suivi par piège photographique) réalisées par le CEN Aquitaine. 57 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 33 records from Plan de gestion des Marais du Conseiller - Inventaire et suivi Faune. 17 records from Projet immobilier sur la commune de Saint-Pierre-d'Irube et le lieu-dit Alminoritz - Inventaire Mammifères. 8 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste RADOGEWSKI Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 99 records from Casual records for Scottish Wildlife Trust reserves - Verified data. 32 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Étude des impacts du Chevreuil de Virginie et du Lièvre d'Amérique à Saint-Pierre et Miquelon (Marcon et al. 2012).. 84 records from Compte-cardobs convention Eurovia - Jeu de données convention Eurovia-SPN-2012-2016. 5 records from Artenvielfalt Kreis Gießen. 5 records from Sargasso 2005 - cetacean sightings. 1342 records from BLM CETAP SHIP Sightings. 5 records from Occurrence of mammalia relicts at site Crumstadt 1. 4 records from Plans de gestion du réseau de sites remarquables en Haute-Vienne - Inventaire initial du plan de gestion : Données bibliographiques. 2371 records from Mamíferos de Nuevo León: distribución y taxonomía. 1 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste SENECAL Didier provenant de la base de donnée du SINP Île-de-France CETTIA. 29 records from Happywhale - Blue Whale in South Atlantic Ocean. 1 records from Umgebung der Grundschule Oderberg. 271 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données d'observateurs divers (observateurs transmettant un nombre de données peu élevé) saisies dans Cettia-idf. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 3 records from Base BOMBINA du Parc Naturel régional Lorraine - Natura 2000 Forêt de la Reine. 13 records from Projet éolien des Marzières - Données brutes de biodiversité. 2 records from Inventaire du canton de Jumilhac en 2001 - Inventaire des espèces patrimoniales et des habitats remarquables. 2573 records from Badger and Habitats Survey of Ireland. 489 records from Ensemble de données récoltées par le Département de la Gironde - Regroupement d'études et inventaires. 202 records from Loup 2010 présence régulière communale (réseau Loup-Lynx ONCFS). 11 records from Registros de murciélagos nativos en una plantación de paltos y almendros, comuna de Paine, Región Metropolitana de Santiago, Chile. 360 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 2018. 9326 records from Biodiversitätsdatenbank Salzburg. 3 records from Happywhale - Steller Sea Lion in North Pacific Ocean. 3 records from Regroupement d'études et inventaires - Données de présence collectées sur la faune patrimoniale. 4611 records from Naturalis Biodiversity Center (NL) - Museum collection digitized at storage unit level. 13 records from Citas de mapache (Procyon lotor) en Bizkaia - Sistema de Información de la Naturaleza de Euskadi. 1 records from Plan de gestion 2015 - 2019 du site du Coteau de Casserouge (47) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 36 records from Animation technique des sites Natura 2000 ‘Barthes de l'Adour’ - Animation des Docobs des barthes de l'Adour 2008-2017. 55 records from Opportunistic marine mammal sightings near Pemba, Mozambique. 173 records from CRESLI marine mammal observations from whale watch cruises 2020. 7 records from (Table 1) Biometrics and lipid content of polar bear (Ursus maritimus) adipose tissue between 1991-2007. 3 records from Expertise IQE - SEDA 2018 - Données Espèces - IQE SEDA 2018. 14 records from Renouvellement et extension d’une carrière / Exploitation d'une installation de concassage-criblage / Déviation d'une voie communale - Inventaires écologiques étude impact carrière de Bagnac sur Célé. 20 records from SILENE-FAUNE-PACA - Gaïadomo_2017_12_18. 8366 records from University of Alberta Museum of Zoology Mammalogy Collection (UAMZ). 69 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Occasionnelle du Loup en 2000. 2471 records from Wildlife diversity of the Dogo-Kétou forest (Benin, West Africa). 31 records from Biodiversidad asociada al Estudio de Impacto Ambiental del campo de producción Cumanday. 14 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi transparence Chiroptères. 737 records from NE Scotland marine mammal records 1800-2010. 4 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Pierre NOEL (M2MNHN2010). 14 records from Atlas écologique régional des papillons de jour et zygènes (Lépidoptères) de Midi-Pyrénées - Données de l'Atlas écologique régional des papillons de jour et zygènes. 5 records from La Planète Revisitée - Guyane 2014/2015 - La Planète Revisitée, massif du Mitaraka, mission principale (février-mars 2015). 131 records from CLICNAT- Base de données naturaliste picarde - Signalements mammifères marins échoués (réellement ou juste posés), Réseau National Echouage. 140 records from Réserves Naturelles de France (RNF) - RNF - Données du Conservatoire d'espaces naturel Limousin. 120994 records from AMNH Mammal Collections. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Emmanuel LESUISSE. 143 records from Manx Biological Recording Partnership VERIFIED Isle of Man records between 14/02/2017 and 05/09/2019. 2 records from SILENE-FAUNE-PACA - AIRELE_2017_12_18. 3 records from Cellule d'Assistance Technique Zones Humides des Pyrénées-Atlantiques (CATZH64) du CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 189 records from Arctic Species Trend Index (ASTI) : Freshwater. 27592 records from Brigham Young University Life Science Museum (BYU) Mammal Collection (Arctos). 13 records from Partenariat avec la Communauté de Communes du Seignanx - Inventaire de la petite faune urbaine dans le cadre du programme de TEPCV du Seignanx. 3187 records from Bernice P. Bishop Museum. 1 records from Projet de centrale photovoltaïque de Palaja - Aude (11) - Inventaire des mammifères terrestres pour le projet PV de Palaja (11). 8072 records from NOAA Atlantic bottlenose dolphin sightings in the coastal and estuarine waters near Charleston, SC - 1994-2011. 1425 records from Natural England Marine Monitoring surveys. 1 records from Inventaires sur le réseau Aquitaine Nature du PNR Périgord-Limousin - Inventaires sur la lande de Moussigou par le CEN Aquitaine. 6 records from Observations de cétacés à partir de campagne aérienne - Observations de cétacés de la campagne aérienne ATLANCET - Observatoire PELAGIS. 2 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Pascal TARTARY. 97 records from Occurrence of mammalia relicts at site Pestera Cioarei. 1 records from Marine Species Records from Skomer Marine Conservation Zone (MCZ) Marine Monitoring Programme. 52 records from Inventarios de fauna y flora en los DRMIs Embalse Peñol - Guatapé y Cuenca Alta del Río Guatapé, Las Camelias y el área a declarar Cuenca de San Pedro. 46 records from Vertebrate specimens of Iwate Prefectural Museum. 111 records from Зимние маршрутные учеты в природном парке «Нумто» (Ханты-Мансийский Автономный Округ). 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Martin HILAIRE. 2 records from Données espèces - Expertise IQE 20. 1 records from Occurrence of mammalia relicts at site Aveley. 417 records from Loup 2016 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 4 records from Avistamiento de fauna marina desde la embarcación en la Expedición de Montes Submarinos 2021. 6 records from Collection of Animal Cell Culture. 3 records from Mutualisation des données ZNIEFF en ex-Limousin - Données indépendante d'Ellen Le Roy. 5 records from Marybio Foundation marine mammal aerial sightings in Bahia San Antonio, Patagonia 2008-2010. 3622 records from Marine mammal monitoring from coastal sites in Cardigan Bay, UK, 2004-2009. 1664 records from MBML-Mamiferos - Coleção de Mamíferos. 1 records from Occurrence of mammalia relicts at site Ceremosnica. 1 records from Stadtbiotop Ulrichteich. 23 records from ONCFS Réseau Ours brun - Ours 2016 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 20 records from Données opportunistes de la Réserve Naturelle Nationale de l'étang de la Mazière. 55 records from Importancia del Parque Estatal Cerro de la Tortuga para la conservación de los mamíferos del estado de Morelos, México. 3 records from Collection contest. 11 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Willy CHENEAU. 77 records from Inventario nacional de especies vegetales y animales de uso artesanal. 5589 records from LTER Antarctic satellite telemetry of humpback whales. 20 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Naturalia_2017_12_18. 1 records from Stadtpark Schmölln. 1 records from Enquête sur 3 mammifères protégés : le Muscardin, le Campagnol amphibie et la Crossope aquatique - Données mammifères Phase 1 récoltées par Vienne Nature. 30 records from Welsh Invertebrate Database (WID). 197 records from Fototrampeo de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 1 records from Plan de gestion 2016 - 2020 du site des Berges de l'Arlas et du Luy de Béarn (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 205 records from AMAPPS Northeast Aerial Cruise Spring 2017. 2 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur PRESSE Tony. 23 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Bulletin mensuel de la société linnéenne de Lyon [1932- ]. 78 records from Opération d'aménagement Vallée Créative - Bordeaux Métropole - Inventaire Faune. 166 records from Water vole survey of Beinn Eighe National Nature Reserve - October 2011. 110 records from AMAPPS Southeast Aerial Cruise Summer 2010. 929 records from Ensemble de données récoltées par le Département de la Gironde - Données opportunistes. 8 records from Caracterización de la diversidad de mamíferos del Parque Tecnológico Ambiental Antanas (PTAA), Pasto - Nariño. 164 records from Regroupement d'études et inventaires de la Réserve Naturelle de l'Etang des Landes - FR3600158 - Ensemble des données. 15 records from Évaluation et préservation de la biodiversité dans les anciennes carrières de Charente-Maritime - Inventaire Faune. 2464 records from Données du Réseau d'observateurs des mammifères marins en mer de la Manche. 24 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Mamíferos marinos Chetumal). 8 records from Observations naturalistes hors étude réalisées par les organismes utilisant la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques hors étude réalisées par Nature en Périgord. 11 records from Evaluation de la qualité du bocage par le biais de suivis du Muscardin - Inventaire Muscardin. 33 records from fauna_do_municipio_de_araraquara-sp. 2 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Pierre FRAPA. 1 records from Naturpark Kottenforst-Ville 16.6.09. 392 records from NMML Small Cetacean Aerial Survey 1999. 7 records from Création d'un centre de stockage de déchets inertes au lieu-dit des Bouquets à Urrugne - Inventaire Faune. 6 records from Herdengelhoehle taxa and datings. 1 records from WADFW PSAMP S1993. 1 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Métropole_Nice_Côte_d'Azur_2017_12_18. 1 records from Natur aus zweiter Hand am Muldestausee. 2801 records from BRERC Notable Species records within the last 10 years. 12 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaire Pic noir et Pic mar sur la ZPS Massif de Fontainebleau. 194 records from Programa de monitoreo comunitario de biodiversidad en RNSC de las veredas Altagracia y Porvenir del Gauchiría, Trinidad, Casanare.. 1 records from WADFW PSAMP W2001. 257 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Occasionnelle du Loup en 2016. 6 records from Kinderbauernhof Pinke-Panke. 1 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 995 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 10 records from Occurrence of mammalia relicts at site Kniegrotte. 13 records from Centralisation des données d'études sur le territoire de la Communauté de Communes de la Côte d'Albâtre. 69 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste MUNIER THIERRY provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Cellule d'Assistance Technique Landes et Pelouses Sèches des Pyrénées-Atlantiques (CATLPS64) du CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 121 records from Whale log - observations from ANARE voyages. 117 records from Muskox Abundance. 1 records from Umgebung von Schorndorf. 1726 records from Rothschild’s Giraffe occurrence records observed at Ruma National Park in the South Western part of Kenya. 3 records from Caracterización biológica de la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 3 records from Données espèces - Expertise IQE 122. 1 records from Synthèse de la répartition des populations de cerf élaphe en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1255 records from MMS High Altitude Survey 1980-1983. 1 records from Stadtpark Herzberg (Elster). 8 records from Expedition "Schulgelände". 68 records from Reef Life Survey: Global reef fish dataset. 3 records from Stausee (Oberdigisheim/Meßstetten). 5 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Philippe GOURSAUD. 25 records from Auswildlife. 3626 records from Northern Territory Museum and Art Gallery provider for OZCAM. 4 records from Médiation Faune Sauvage - Inventaire de données. 19 records from PSUZC-Mammal Collection. 8 records from NEFSC Survey 1997. 372 records from Proyecto COL88611 para la conservación y uso sostenible de ecosistemas secos. 4777 records from Vertebrats d'Andorra. 586 records from Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 384 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 2019. 17 records from Inventory animals of Déve and Togbadji sites in the Mono department Benin. 5 records from Happywhale - Short-finned Pilot Whale in South Pacific Ocean. 4 records from Yorkshire Naturalists Union Marine and Coastal Section Records. 58 records from Animation du site Natura 2000 " Les Caves de Nérac " (FR7200800) - Suivis des Chiroptères sur le territoire Natura 2000 (FR7200800). 30 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Guillaume MARCHAIS. 115 records from Species within North Ayrshire from 1984 - Present. 1 records from Diagnostic préalable pour l’élaboration du DOCOB du site Natura 2000 ‘Forêts dunaires de La Teste-de-Buch’ (FR7200702) - Inventaire écologique. 16 records from Occurrence of mammalia relicts at site la Grotte du Thai. 1 records from Plan de gestion 2014 - 2018 de la Réserve Naturelle Régionale des carrières de Tercis-les-Bains (40) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 3 records from Convention Fédération française de golf - MNHN 2016-2019 - IPS Golfs. 2 records from Südpark (Bochum-Wattenscheid). 37 records from Lemur_occurrences_Madagasikara_Voakajy_MLP_20190917. 16 records from Données brutes de biodiversité du projet éolien de la Bénitière. 167 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 2010. 13060 records from Israel Nature and Parks Authority. 9 records from NMML Harbor Porpoise Aerial Survey, Bristol Bay, Replicate 2, 1991. 1 records from Inventaire permanent des ZNIEFF de Poitou-Charentes - Inventaire de données en Charente-Maritime. 207 records from NEFSC Aerial Survey - Experimental 2002. 7 records from Bat collection of Bats Ecology and Conservation Lab, Universiti Sains Malaysia. 1 records from Monitoreo de peces arrecifales y tiburones parte de los valores objetos de conservación (VOC) en el santuario Malpelo para el año 2020. 612 records from Colección de Mamíferos (Mammalia) del Museo de Historia Natural de la Universidad de Caldas, Colombia. 26 records from Occurrence of mammalia relicts at site Falkensteinhöhle. 76 records from Records at sea of juveniles southern elephant seals (Mirounga leonina) from Península Valdés, Argentina. 824 records from Northern Elephant Seals Post-Molting 2016 (aggregated per 1-degree cell). 271 records from Estudio taxonómico de las aves y mamíferos del Valle Cuatrociénegas, Coahuila, México. 18 records from Mastofauna presente en el Alto del Buey, Bahía Solano, Chocó. 2 records from Notice de gestion 2014 - 2018 de la bande de servitude de l'artère Girland (40) de Teréga mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 2 records from Tag der Artenvielfalt. 1 records from Occurrence of mammalia relicts at site Vjetrenica Höhle. 8 records from Occurrence of mammalia relicts at site Joint Mitnor Cave. 1 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 396 records from Collecte permanente de données naturalistes sur la base de donnée participative en ligne de Vienne Nature (Fnat) - Synthèse 10x10km de la faune sauvage de la Directive Habitats-Faune-Flore recensée par l'association Vienne Nature de 2013 à 2017. 1 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" de l'étang d'Hardy (SOUSTONS). 20 records from Chronicle of Nature - Phenology of Mammals of Kondinskie Lakes National Park named after L. F. Stashkevich. 195 records from Données Faune de l'Agence des Espaces Verts (AEV) d'Ile de France. 5 records from The Wildlife Information Centre - BioBlitz Events. 1 records from Red Sea Cetacean Review - Strandings. 1651 records from Northern Ireland Environment Agency (NIEA) Collated Species Records. 391 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 4 records from Occurrence of mammalia relicts at site Luttenberg. 3 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Ouest aménagement provenant de la base de donnée du SINP Île-de-France CETTIA. 37 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Audrey SAVOURE-SOUBELET. 3126 records from National Trust Species Records. 16309 records from Australian National Wildlife Collection provider for OZCAM. 3 records from Projet éolien de Camblain-Châtelain (SEPE Le Mont Duquenne) - Amphibiens-mammifères. 168 records from NMML Harbor Porpoise Vessel, SE Alaska, Fall 1993. 2 records from Plan de gestion 2008 - 2012 du Lac de La Prade (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 139 records from SWFSC Marine Mammal Survey, STAR 1998, Cruise 1610. 279 records from Northern Elephant Seals Post-Molting 2017 Guadalupe Island, Mexico (aggregated per 1-degree cell). 20 records from Etat initial de la faune pour la construction de la liaison RD656/RD119 et des carrefours associés (Amorce de la rocade Ouest d'Agen) - Inventaire et suivi Faune. 8 records from Mesures compensatoires routes départementales - Données CEN M-P compensation RD. 12 records from Données espèces - Expertise IQE 92. 9 records from Hydrographic profiles in South West Atlantic Ocean derived from Southern Elephant seals dives. 132 records from SILENE-FAUNE-PACA - DREAL_PACA_2017_12_18. 133 records from Mammal specimens of Saitama Museum of Natural History. 126 records from Fauna y flora asociada a la Central Hidroeléctrica Playas. 46 records from Données LIFE + DESMAN CEN MP. 1 records from Binsenwiesen. 158 records from Gola National Park Biomonitoring Data. 53 records from Antarctic Biodiversity Studies 2006 (Ross Sea, Scott Island, and Balleny Islands) (TAN0602). 1 records from MSB Bird Collection (Arctos). 18 records from Naturhistorisches Museum Mainz, Zoological Collection. 24 records from EDP Foz Tua Otter (Lutra lutra) - Ecological Monitoring Program (2010-11). 30 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure CERF (Centre d'Etude de Rambouillet et de sa Forêt) provenant de la base de donnée du SINP Île-de-France CETTIA. 771 records from Geelong Field Naturalists Club. 14 records from Occurrence of mammalia relicts at site Gönnersdorf. 4 records from Zukünftiges NSG Höftland/Bockholmwik. 7 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de PIOLAIN Julien. 71 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Loïc SALAUN. 15 records from Línea base del medio biótico en los bosques para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguablanca -El Morro Yopal. 44 records from Atlas de la Biodiversité Communales sur la Communauté de Commune de Montesquieu - Données faune opportuniste récoltées en marge des protocoles Amphibien & Reptiles. 2 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Angé christofer provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from Tejidos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 299179 records from Muskrat trapping data in the Netherlands 1987 – 2014. 1 records from Comunidad íctica de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 1 records from Données naturalistes acquises sur les sites du MNHN. 46 records from SEFSC Gomex Shelf 2000. 3 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Wilfried RATEL. 849 records from NEFSC 1999 aj9902. 368 records from Plateforme AUVERGNE-DREAL Auvergne - DREAL Auvergne - Mammifères - 2015. 271 records from Réserves Naturelles de France (RNF) - RNF - Données du Syndicat de Gestion des Gorges de l'Ardêche. 70 records from DUML vessel-based line transect surveys for proposed Onslow Bay USWTR site 2007-2010. 116 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 47 records from Inventario de Aves y Mamíferos en humedales del departamento de Córdoba. 50 records from Bats of Northern Peninsular Malaysia. 35 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Julien BIRARD. 3 records from Données espèces - Expertise IQE 52. 323 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 25 records from Caracterización de Fauna para el plan de Etnodesarrollo de Bahía Cupica, Chocó. 1747 records from PIROP Northwest Atlantic 1965-1992. 6 records from CRC HRC Vessel-Based Surveys KB11 2013-2014. 12 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 1 records from Plan de gestion 2013 - 2018 du Lac de La Prade (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 5 records from Projet d'ouverture d'une gravière sur la commune de St-Michel de Rieufret, lieudits - Données brutes biodiversité - St Michel de Rieufret. 7 records from Systematics, distribution and ecological analysis of rodents in Jordan. 190 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores tuna fishery from 1998 to 2013: while fishing. 9 records from UNCW JAX Aerial Survey - Right side - 2016. 1 records from Steinbachtal (Würzburg). 66 records from Chronicle of Nature - Phenology of Mammals of State Nature Reserve Nurgush. 1 records from Wirbach. 31 records from Mamíferos laguna El Tinije. 6 records from Animation du site Natura 2000 ‘La Vallée de l'Avance’ (FR7200739) - Données opportunistes. 3 records from Construction d'un projet photovoltaïque flottant - Données CALIDRIS. 14 records from Animal Collections Of The Department of Zoology- Nasarawa State University Keffi. 5 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes opportunistes de Cedric DEVILLEGER. 13313 records from Lund Museum of Zoology (MZLU). 7925 records from Happywhale - Humpback Whale in Southern Ocean. 3 records from Centrale photovoltaïque au sol de TIercé - données faune flore, centrale photovoltaïque de Tiercé (49). 513 records from Merseyside BioBank (unverified). 108 records from Réseau Loup - Lynx ONCFS - Lynx 2015 présence Occasionnelle Mailles_10km_LAEA Réseau Loup-Lynx ONCFS. 232 records from CODA cetacean sightings on primary platform of vessel surveys 2007. 22 records from ONCFS Réseau Ours brun - Ours 2001 présence Régulière Mailles 10km LAEA Réseau Ours brun ONCFS. 4 records from Collections paléontologiques de l'Université Rennes 1. 20346 records from Données ONF faune-flore-fonge. 2 records from Observations occasionnelles de taxons par les agents de la Fédération (hors inventaires scientifiques) - Inventaire opportunistes Faune. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 6 records from Occurrence of mammalia relicts at site Trebacki krs. 55 records from Chronicle of Nature - Phenology of Mammals of Baikalsky State Nature Biosphere Reserve. 392 records from Kenneth S. Norris Center for Natural History, University of California, Santa Cruz (UCSC) Mammal specimens (Arctos). 5451 records from NPWS Seal Database. 3 records from Plan de gestion 2013 - 2017 de la base militaire BA120 de Cazaux (33) - Inventaire faunistiques. 127 records from Caracterización de la mastofauna asociada a los bosques secos del Dagua - Valle del Cauca, 2018. 2 records from Mammalia (SMNH-MM). 3 records from Occurrence of mammalia relicts at site Siebenlinden 3. 4 records from Opportunistic records of marine me
Keywords: GBIF; biodiversity; species occurrences